Toner, toner container, and image forming apparatus
Patent Information
- Application Number
- JP2021047487
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-22
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-03-22
AI Technical Summary
【0007】 本発明によると、低温定着性と耐熱保存性とを高レベルに両立することができ、良好なクリーニング性を維持しつつ、フィルミングによる異常画像の発生を抑制できるトナーを提供することができる。
Smart Images

Figure 0007643120000007 
Figure 0007643120000008 
Figure 0007643120000009
Abstract
Description
[Technical field]
[0001] The present invention relates to a toner, a toner storage container, and an image forming apparatus. [Background technology]
[0002] Toners are required to have small particle size and high-temperature offset resistance for high-quality output images, low-temperature fixability for energy saving, and heat-resistant storage stability that can withstand high temperatures and high humidity during storage and transportation after production. In particular, since power consumption during fixation accounts for a large portion of the power consumption in the image formation process, improving low-temperature fixability is extremely important.
[0003] In recent years, in order to obtain a high level of low-temperature fixability, a toner has been proposed that contains a resin including a crystalline polyester resin and a release agent, in which the resin and the wax (release agent) are incompatible with each other and have a sea-island phase-separated structure (see Patent Document 1). In addition, a toner containing a crystalline polyester resin, a release agent, and a graft polymer (see Patent Document 2) and a toner containing predetermined amorphous polyester resins A and B and crystalline polyester resin C, which have excellent low-temperature fixing properties, heat-resistant storage properties, and high-temperature / high-humidity storage properties, have been proposed (see Patent Documents 3 to 5). Furthermore, in order to achieve both low-temperature fixing ability and heat-resistant storage stability, a toner containing a hybrid resin in which a crystalline polyester unit and an amorphous resin unit are chemically bonded has been proposed (see Patent Document 6).
[0004] Furthermore, in order to achieve high heat resistance and toner aggregation during long-term use, a toner has been proposed in which the core layer contains a styrene-acrylic modified polyester resin and is coated with spherical shell particles covered with a styrene-acrylic resin component (see Patent Document 7). In order to obtain a toner binder that has excellent low-temperature fixing properties, heat-resistant storage stability, and a sharp particle size distribution, a method for producing composite resin particles has been proposed, which includes forming composite resin particles in which resin microparticles containing two types of resin as constituent components within the same particle are attached to the surface of the resin particles, and then removing some or all of the resin from the resin microparticles (see, for example, Patent Documents 8 to 10). Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a toner which can achieve both low-temperature fixability and high-temperature storage stability at a high level, maintain good cleanability, and suppress the occurrence of abnormal images due to filming. [Means for solving the problem]
[0006] The toner of the present invention as a means for solving the above problems is A toner having resin particles on the surface of a toner base particle containing at least a crystalline polyester resin, an amorphous polyester resin, a colorant, and a release agent, the maximum diameter of a domain of a crystalline polyester resin of the toner observed by a transmission electron microscope (TEM) is 1.5 μm or less; Among the domains of the crystalline polyester resin present in the toner, a ratio of the domains of the crystalline polyester resin having a maximum diameter of more than 1.0 μm is 10% or less, The toner is characterized in that the standard deviation of the distance between adjacent resin particles that are not in contact with each other and that are present on the surface of the toner base particle is less than 600 nm. Effect of the Invention
[0007] According to the present invention, it is possible to provide a toner which can achieve both low-temperature fixability and high-temperature storage stability at a high level, maintain good cleaning properties, and suppress the occurrence of abnormal images due to filming. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a TEM image showing an example of a cross-sectional state of the toner of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing an example of an image forming apparatus according to the present invention. [Diagram 3] FIG. 3 is a schematic view showing an example of the process cartridge of the present invention. [Figure 4] FIG. 4 is a diagram showing an example of the state of resin particles on the toner surface in the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] (toner) The toner of the present invention is a toner having resin particles on the surface of toner base particles containing at least a crystalline polyester resin, an amorphous polyester resin, a colorant, and a release agent, wherein the maximum diameter of a crystalline polyester resin domain of the toner observed by a transmission electron microscope (TEM) is 1.5 μm or less, the proportion of the crystalline polyester resin domains having a maximum diameter of the crystalline polyester resin domain exceeding 1.0 μm among the crystalline polyester resin domains present in the toner is 10% or less, the standard deviation of the distance between adjacent resin particles present on the surface of the toner base particles that are not in contact with each other is less than 600 nm, and further contains other components as necessary.
[0010] Generally, in order to improve the low-temperature fixing property of a toner, it is necessary to use a material having a low melting point for the toner, but a toner produced using a material having a low melting point has poor heat-resistant storage stability, and therefore it is known that there is a trade-off between low-temperature fixing property and heat-resistant storage stability. Conventional toners contain a hybrid resin, which allows the crystalline polyester resin to be uniformly dispersed inside the toner, improving low-temperature fixability. However, there is a problem in that the crystalline polyester resin exposed on the toner surface deteriorates the heat-resistant storage stability of the toner, and it has been insufficient to achieve both low-temperature fixability and heat-resistant storage stability, which are required in recent years. In addition, conventional toners are covered with particles having a structure (core-shell structure) in which a styrene acrylic modified polyester resin, which is a core layer, is covered with a styrene acrylic resin component (shell layer), so that electrostatic aggregation does not occur even with long-term continuous use, and image spot failures can be suppressed. However, there was a problem that the shell layer in the core-shell structure inhibits heat conduction during fixing, making it impossible to obtain sufficient low-temperature fixing properties.
[0011] For the purpose of imparting fluidity and chargeability to a toner, a process of treating the surface of the toner with an external additive made of inorganic fine particles such as silica or titanium oxide is widely used. Usually, the image carrier in an image forming apparatus is cleaned by blocking and removing the residual toner on the image carrier with a cleaning blade. At that time, a part of the external additive is liberated from the toner blocked on the image carrier by the cleaning blade. The liberated external additive is supplied to the contact portion between the cleaning blade and the image carrier, and a reservoir layer of the external additive is formed. The reservoir layer acts as a lubricant between the cleaning blade and the image carrier, and good cleaning performance can be obtained. However, conventional toners have a problem that the external additive is liberated too much, which easily causes abnormal images due to filming.
[0012] As a result of intensive research, the present inventors have found that a toner having resin particles on the surface of a toner base particle containing at least a crystalline polyester resin, an amorphous polyester resin, a colorant, and a release agent, the maximum diameter of the crystalline polyester resin domain observed by a transmission electron microscope (TEM) of the toner is 1.5 μm or less, and the ratio of the crystalline polyester resin domains having a maximum diameter of the crystalline polyester resin domain exceeding 1.0 μm among the domains of the crystalline polyester resin present in the toner is 10% or less, thereby making it possible to achieve both low-temperature fixability and heat-resistant storage stability at a high level.Furthermore, the present inventors have found that the occurrence of abnormal images due to filming can be suppressed while maintaining low-temperature fixability, heat-resistant storage stability, and good cleanability by making the standard deviation of the distance between the adjacent resin particles present on the surface of the toner base particle that are not in contact with each other less than 600 nm.
[0013] Therefore, in the present invention, a toner having resin particles on the surface of toner base particles containing at least a crystalline polyester resin, an amorphous polyester resin, a colorant, and a release agent, wherein the maximum diameter of a crystalline polyester resin domain of the toner observed by a transmission electron microscope (TEM) is 1.5 μm or less, the proportion of the crystalline polyester resin domains having a maximum diameter of the crystalline polyester resin domain exceeding 1.0 μm among the crystalline polyester resin domains present in the toner is 10% or less, and the standard deviation of the distance between adjacent resin particles present on the surface of the toner base particles that are not in contact with each other is less than 600 nm, thereby making it possible to achieve a high level of both low-temperature fixability and heat-resistant storage stability, and to suppress the occurrence of abnormal images due to filming while maintaining good cleanability.
[0014] [Toner base particles] The toner base particles (hereinafter sometimes referred to as “toner base” or “base particles”) contain a crystalline polyester resin, an amorphous polyester resin, a colorant, and a release agent, and further contain an amorphous hybrid resin and other component A, as necessary.
[0015] <Crystalline polyester resin> The toner of the present invention contains a crystalline polyester resin. When the crystalline polyester resin is used in combination with an amorphous polyester resin described below, the following properties are obtained. The crystalline polyester resin has high crystallinity and therefore has excellent heat resistance and storage stability up to just before the melting start temperature (fixing start temperature). When the melting start temperature is reached, the resin exhibits a heat melting characteristic (sharp melting property) in which the viscosity is rapidly decreased. At that time, the resin is compatible with the amorphous polyester resin, and the viscosity of the amorphous polyester resin is rapidly decreased along with the crystalline polyester resin. The decrease in the viscosity of the crystalline polyester resin and the amorphous polyester resin allows the toner to be fixed. That is, by using the crystalline polyester resin and the amorphous polyester resin together, a toner having both good heat-resistant storage stability and low-temperature fixability can be obtained.
[0016] The crystalline polyester resin can be obtained from a polyhydric alcohol and a polycarboxylic acid or a derivative thereof, such as a polycarboxylic acid, a polycarboxylic anhydride, or a polycarboxylic ester. In the present invention, the crystalline polyester resin refers to a resin obtained by using a polyhydric alcohol and a polycarboxylic acid or a derivative thereof, such as a polycarboxylic acid, a polycarboxylic anhydride, or a polycarboxylic acid ester, as described above. For example, a modified polyester resin, a prepolymer described below, or a resin obtained by subjecting the prepolymer to a crosslinking and / or elongation reaction does not belong to the crystalline polyester resin.
[0017] -Polyhydric alcohol- The polyhydric alcohol is not particularly limited and can be appropriately selected depending on the purpose. Examples of the polyhydric alcohol include diols and trihydric or higher alcohols.
[0018] --Diol-- The diol is not particularly limited and can be appropriately selected depending on the purpose. Examples of the diol include saturated aliphatic diols. The saturated aliphatic diol is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include linear saturated aliphatic diols, etc. Among these, linear saturated aliphatic diols are preferred, and linear saturated aliphatic diols having 2 to 12 carbon atoms are more preferred. These may be used alone or in combination of two or more. If the saturated aliphatic diol is a branched type, the crystallinity of the crystalline polyester resin may decrease, resulting in a decrease in melting point. If the saturated aliphatic diol has more than 12 carbon atoms, it becomes difficult to obtain a practical material.
[0019] Specific examples of the saturated aliphatic diol include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, 1,14-eicosanediol, etc. Among these, ethylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, and 1,12-dodecanediol are preferred in terms of obtaining high crystallinity and excellent sharp melting properties in the crystalline polyester resin. These may be used alone or in combination of two or more.
[0020] --Trivalent or higher alcohols-- The trihydric or higher alcohol is not particularly limited and can be appropriately selected depending on the purpose. Examples of the trihydric or higher alcohol include glycerin, trimethylolethane, trimethylolpropane, and pentaerythritol. These may be used alone or in combination of two or more.
[0021] -Polycarboxylic acids- The polyvalent carboxylic acid is not particularly limited and can be appropriately selected depending on the purpose. Examples of the polyvalent carboxylic acid include divalent carboxylic acids and trivalent or higher carboxylic acids. These may be used alone or in combination of two or more.
[0022] --Dicarboxylic acid-- The divalent carboxylic acid is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include saturated aliphatic dicarboxylic acids such as oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, and 1,18-octadecanedicarboxylic acid; and aromatic dicarboxylic acids such as dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, malonic acid, and mesaconic acid.Furthermore, anhydrides thereof and lower (1 to 3 carbon atoms) alkyl esters thereof can also be mentioned. These may be used alone or in combination of two or more.
[0023] --Trivalent or higher carboxylic acids-- The trivalent or higher carboxylic acid is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include 1,2,4-benzenetricarboxylic acid, 1,2,5-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc. Further examples include anhydrides thereof and lower (carbon number 1 to 3) alkyl esters thereof. These may be used alone or in combination of two or more.
[0024] The polyvalent carboxylic acid may include a dicarboxylic acid having a sulfonic acid group in addition to the saturated aliphatic dicarboxylic acid and the aromatic dicarboxylic acid. The polyvalent carboxylic acid may include a dicarboxylic acid having a double bond in addition to the saturated aliphatic dicarboxylic acid and the aromatic dicarboxylic acid.
[0025] The crystalline polyester resin is preferably composed of a linear saturated aliphatic dicarboxylic acid having 4 to 12 carbon atoms and a linear saturated aliphatic diol having 2 to 12 carbon atoms. That is, the crystalline polyester resin preferably has a structural unit derived from a saturated aliphatic dicarboxylic acid having 4 to 12 carbon atoms and a structural unit derived from a saturated aliphatic diol having 2 to 12 carbon atoms. By doing so, the crystalline polyester resin has high crystallinity and excellent sharp melting properties, and therefore a toner exhibiting excellent low-temperature fixing properties can be obtained.
[0026] The melting point of the crystalline polyester resin is not particularly limited and may be appropriately selected depending on the purpose, but is preferably 60° C. or more and 80° C. or less. If the melting point of the crystalline polyester resin is less than 60° C., the crystalline polyester resin is likely to melt at low temperatures, and the heat-resistant storage stability of the toner may decrease. If the melting point of the crystalline polyester resin is more than 80° C., the crystalline polyester resin may not melt sufficiently due to heating during fixing, and the low-temperature fixability may decrease.
[0027] The molecular weight of the crystalline polyester resin is not particularly limited and can be appropriately selected depending on the purpose. However, it is preferable that the molecular weight is within the following range because a resin having a sharp molecular weight distribution and a low molecular weight has excellent low-temperature fixability, and because a large amount of low-molecular weight components reduces heat-resistant storage stability. The weight average molecular weight (Mw) of the orthodichlorobenzene soluble portion of the crystalline polyester resin, as measured by gel permeation chromatography (GPC), is preferably 3,000 or more and 30,000 or less, and more preferably 5,000 or more and 15,000 or less. The number average molecular weight (Mn) of the orthodichlorobenzene soluble portion of the crystalline polyester resin, as measured by gel permeation chromatography (GPC), is preferably 1,000 or more and 10,000 or less, and more preferably 2,000 or more and 10,000 or less. In the measurement by gel permeation chromatography (GPC), the weight average molecular weight (Mw) / number average molecular weight (Mn) of the orthodichlorobenzene soluble portion of the crystalline polyester resin is preferably 1.0 or more and 10 or less, and more preferably 1.0 or more and 5.0 or less.
[0028] In the present invention, the weight average molecular weight (Mw) and the number average molecular weight (Mw) can be measured by gel permeation chromatography (GPC) under the following conditions. -Measurement conditions- Equipment (example): "HLC-8120" (manufactured by Tosoh Corporation) Column (example): 2 "TSK GEL GMH6" (Tosoh Corporation) ·Measurement temperature 40℃ Sample solution: 0.25% by weight tetrahydrofuran solution (insolubles were filtered off using a glass filter) ·Solution injection volume 100μL -Detection device: Refractive index detector Standard material: 12 standard polystyrenes (TSKstandard POLYSTYRENE) (molecular weight: 500, 1,050, 2,800, 5,970, 9,100, 18,100, 37,900, 96,400, 190,000, 355,000, 1,090,000, 2,890,000) (manufactured by Tosoh Corporation)
[0029] The acid value of the crystalline polyester resin is not particularly limited and can be appropriately selected depending on the purpose, but from the viewpoint of obtaining affinity between the paper and the resin and the desired low-temperature fixability, it is preferably 5 mgKOH / g or more, more preferably 10 mgKOH / g or more. Note that, from the viewpoint of improving high-temperature offset resistance, it is preferably 45 mgKOH / g or less.
[0030] The hydroxyl value of the crystalline polyester resin is not particularly limited and may be appropriately selected depending on the purpose. In order to obtain the desired low-temperature fixing property and good charging characteristics, the hydroxyl value is preferably from 0 mgKOH / g to 50 mgKOH / g, and more preferably from 5 mgKOH / g to 50 mgKOH / g.
[0031] The content of the crystalline polyester resin is not particularly limited and can be appropriately selected according to the purpose, but in terms of improving image quality and excellent low-temperature fixing property, it is preferably 3 parts by mass or more and 20 parts by mass or less, and more preferably 5 parts by mass or more and 15 parts by mass or less, relative to 100 parts by mass of the toner. If the content of the crystalline polyester resin is less than 3 parts by mass, the sharp melting by the crystalline polyester resin is insufficient, so that the low-temperature fixing property may be poor. If the content of the crystalline polyester resin is more than 20 parts by mass, the heat-resistant storage stability may decrease and the image may be easily fogged.
[0032] The presence or absence of crystallinity of the crystalline polyester resin in the toner of the present invention can be confirmed by a crystal analysis X-ray diffraction device (for example, X'Pert Pro MRD Philips). The measurement method is shown below. First, the target sample is ground in a mortar to prepare a powdered sample, and the powdered sample is evenly applied to a sample holder.Then, the sample holder is set in the diffraction device, and measurements are performed to obtain a diffraction spectrum. When the half-width of the peak having the greatest intensity among the obtained diffraction peaks in the range of 20°<2θ<25° is 2.0 or less, the target sample is determined to be crystalline. In contrast to crystalline polyester resins, polyester resins that do not exhibit the above-mentioned state are referred to as amorphous polyester resins in the present invention. The measurement conditions for X-ray diffraction are described below. -Measurement conditions- Tension kV: 45kV Current: 40mA ·MPSS Upper Gonio Scan mode: continuous Starting angle: 3° End angle: 35° Angle Step: 0.02° Lucident beam optics ·Divergence slit: Div slit 1 / 2 Diffraction beam optics ·Anti scatter slit: As fixed 1 / 2 ·Receiving slit: Prog rec slit
[0033] The molecular structure of the crystalline polyester resin can be confirmed by NMR measurement of a solution or solid, as well as X-ray diffraction, GC / MS, LC / MS, IR measurement, etc. -1 Or 990±10cm -1 One method is to detect a crystalline polyester resin that has absorption based on the δCH (out-of-plane bending vibration) of olefin.
[0034] The domain of the crystalline polyester resin in the present invention refers to the crystalline polyester resin that exists independently in the toner.
[0035] <Maximum diameter of domain of crystalline polyester resin> In the present invention, the "maximum diameter of the domain of the crystalline polyester resin" refers to the maximum of the major axes of the domain of the crystalline polyester resin determined from a TEM image obtained by the method described below. Specifically, TEM images of the cross sections of 100 toner particles are created using the method described below, and the major axis of all crystalline polyester resin domains present in the cross sections of the 100 toner particles is measured using the image processing software "Image-J." The largest of the obtained measurements is taken as the maximum diameter of the crystalline polyester resin domain. When the domain of the crystalline polyester resin is amorphous, the measurement method that gives the longest diameter is adopted, and this is regarded as the maximum diameter of the domain of the crystalline polyester resin.
[0036] In the toner of the present invention, the maximum diameter of the domain of the crystalline polyester resin observed by a transmission electron microscope (TEM) is 1.5 μm or less, and more preferably, the maximum diameter of the domain of the crystalline polyester resin is 1.2 μm or less. If the maximum diameter of the domain of the crystalline polyester resin exceeds 1.5 μm, the crystalline polyester resin melts locally inside the toner, causing unevenness in the melted state inside the toner, which causes deterioration of storage stability.
[0037] In the toner of the present invention, the proportion of the crystalline polyester resin domains having a maximum diameter exceeding 1.0 μm among the crystalline polyester resin domains present in the toner is 10% or less.Furthermore, it is preferable that the proportion of the crystalline polyester resin domains having a maximum diameter exceeding 1.0 μm is 5% or less. If the ratio of domains of the crystalline polyester resin having a maximum domain diameter exceeding 1.0 μm exceeds 10%, the crystalline polyester resin melts locally within the toner, causing unevenness in the melted state within the toner, which causes deterioration of storage stability. The proportion of the crystalline polyester resin domains in the toner having a maximum diameter of more than 1.0 μm can be adjusted by appropriately changing the dispersion conditions in the dispersion process of the crystalline resin.
[0038] -Method for observing domains in crystalline polyester resin- The domains of the crystalline polyester resin contained in the toner of the present invention can be observed by staining the toner with ruthenium and then using a TEM (transmission electron microscope). When the toner is dyed with ruthenium, the crystalline polyester resin contained in the toner has a high contrast and is easy to observe. When ruthenium dyeing is used, the amount of ruthenium atoms varies depending on the strength of the dyeing, so that the strongly dyed parts have a large amount of these atoms, and the electron beam does not pass through them, so they appear black in the observation image, while the weakly dyed parts have an electron beam that easily passes through them, so they appear white in the observation image. Specifically, the crystalline polyester resin is dyed weaker than the other organic components constituting the toner. This is thought to be because the dyeing material penetrates weaker into the crystalline polyester resin than the other organic components constituting the toner due to differences in density, etc. Ruthenium that does not penetrate into the crystalline polyester resin tends to remain at the interface between the crystalline polyester resin and the amorphous polyester resin, and when the crystals are needle-shaped, the crystalline polyester resin is observed to be black. An example of a procedure for preparing a cross section of a ruthenium-dyed toner will be described below. --Sample preparation-- (1) The toner is thoroughly dispersed in a room temperature curing epoxy resin (Devcon DEV-TUBE), and then the mixture is left for at least one day to cause a curing reaction of the epoxy resin, thereby obtaining a cured material with the toner embedded therein. (2) Using a microtome (Leica EM UC7) equipped with a diamond blade, the cross section of the cured material is exposed, and the cured material with the cross section exposed is immersed for 3 hours in an organic solvent (hexane) in which only the release agent dissolves, thereby dissolving only the domains of the release agent. (3) After that, the hardened product is dried for at least one day, and then a thin film slice is cut out under the cutting conditions described below, and the obtained thin film slice is stained with ruthenium tetroxide. -Cutting conditions- Cutting thickness: 100nm ·Cutting speed 0.05~0.2 mm / sec Uses a diamond knife (Ultra Sonic 35°) The slice was adjusted so that one slice contained cross sections of about 50 toner particles or toner particles.
[0039] A cross-sectional image of the toner is taken at a magnification of 30,000 times using a transmission electron microscope (TEM). By staining with ruthenium tetroxide, components with different degrees of crystallinity contained in the toner are stained with contrast, making it possible to identify the domains of the crystalline polyester resin contained in the toner. As shown in the dotted line area in FIG. 1, linear or lamellar crystals scattered within the amorphous polyester resin in the TEM image after binarization can be determined to be crystalline polyester resin. The observation using a transmission electron microscope can be performed, for example, according to the conditions shown below. --Observation conditions-- Equipment: JEOL Transmission Electron Microscope JEM-2100F Acceleration voltage: 200kV Morphological observation: bright field method ·Setting conditions spot size:3,CLAP:1,OLAP:3,Alpha:3 The obtained TEM image is binarized (threshold 80 / 255 steps) using the image analysis software "Image-J". After binarization, the area surrounded by a black border is the domain derived from the crystalline polyester. Note that the major axis of the toner in the TEM image corresponds to the average particle diameter of the produced toner.
[0040] The maximum diameter of the domain of the crystalline polyester resin in the present invention can also be confirmed by, for example, a phase image by tapping mode in a scanning probe microscope (e.g., atomic force microscope (AFM)). The tapping mode in AFM is a method described in Surface Science Letter, 290, 668 (1993). In this method, as described in, for example, Polymer, 35, 5778 (1994) and Macromolecules, 28, 6773 (1995), the shape of the sample surface is measured while vibrating the cantilever. At this time, due to the viscoelastic properties of the sample surface, a phase difference occurs between the drive, which is the source of the cantilever vibration, and the actual vibration. The phase image is a mapping of this phase difference. A soft portion is observed to have a large phase delay, and a hard portion is observed to have a small phase delay. In general, since the crystalline polyester resin is relatively softer than the binder resin, it is possible to identify a portion with a large phase difference as a domain of the crystalline polyester resin. The sample for obtaining the phase image can be prepared by a method similar to that used for observation with a transmission electron microscope, and a representative device for obtaining the phase image with an AFM is, for example, the MFP-3D manufactured by Asylum Technology. The cantilever may be, for example, OMCL-AC240TS-C3. The measurement conditions are as follows. -Measurement conditions- Target amplitude: 0.5V target percent: -5% Amplitude setpoint: 315mV Scan rate: 1Hz Scan points: 256×256 Scan angle: 0°
[0041] <Amorphous polyester resin> The toner of the present invention contains an amorphous polyester resin (hereinafter, may be referred to as "amorphous polyester", "amorphous polyester", or "amorphous polyester resin"). The amorphous polyester resin preferably contains a modified polyester resin.
[0042] The amorphous polyester resin is not particularly limited and can be appropriately selected depending on the purpose. For example, it can be obtained by reacting a polyol with a polycarboxylic acid. In the present invention, the amorphous polyester resin refers to a resin obtained by reacting a polyol with a polycarboxylic acid as described above. For example, a polyester resin modified, a prepolymer described below, and a modified polyester resin obtained by subjecting the prepolymer to a crosslinking and / or elongation reaction are not included in the amorphous polyester resin in the present invention, and are treated as modified polyester resins. The amorphous polyester resin is a polyester resin component that is soluble in tetrahydrofuran (THF).
[0043] -Polyol- The polyol is not particularly limited and can be appropriately selected depending on the purpose. Examples of the polyol include diols. The diol is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include alkylene (carbon number 2-3) oxide (average added mole number 1-10) adducts of bisphenol A such as polyoxypropylene (2.2)-2,2-bis(4-hydroxyphenyl)propane and polyoxyethylene (2.2)-2,2-bis(4-hydroxyphenyl)propane: ethylene glycol, propylene glycol, hydrogenated bisphenol A, and alkylene (carbon number 2-3) oxide (average added mole number 1-10) adducts of hydrogenated bisphenol A. Among these, it is preferable that the polyol contains 40 mol % or more of alkylene glycol. These may be used alone or in combination of two or more.
[0044] -Polycarboxylic acid- The polycarboxylic acid is not particularly limited and can be appropriately selected depending on the purpose. Examples of the polycarboxylic acid include dicarboxylic acids. The dicarboxylic acid is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include adipic acid, phthalic acid, isophthalic acid, terephthalic acid, fumaric acid, maleic acid, dodecenylsuccinic acid, octylsuccinic acid, and other alkyl groups having 1 to 20 carbon atoms; succinic acid substituted with an alkenyl group having 2 to 20 carbon atoms; etc. Among these, the polycarboxylic acid preferably contains 50 mol % or more of terephthalic acid. These may be used alone or in combination of two or more.
[0045] The amorphous polyester resin may contain a trivalent or higher carboxylic acid and / or a trivalent or higher alcohol, a trivalent or higher epoxy compound, etc. at the end of the resin chain in order to adjust the acid value and hydroxyl value. Among these, it is preferable to contain a trivalent or higher aliphatic alcohol from the viewpoint of preventing unevenness and obtaining sufficient gloss and image density. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, and acid anhydrides thereof. These may be used alone or in combination of two or more. Examples of the trihydric or higher alcohol include glycerin, pentaerythritol, and trimethylolpropane. These may be used alone or in combination of two or more.
[0046] The molecular weight of the amorphous polyester resin is not particularly limited and may be appropriately selected depending on the purpose, but is preferably within the following range. The weight average molecular weight (Mw) of the amorphous polyester resin is preferably 3,000 or more and 10,000 or less, and more preferably 4,000 or more and 7,000 or less. The number average molecular weight (Mn) of the amorphous polyester resin is preferably 1,000 or more and 4,000 or less, and more preferably 1,500 or more and 3,000 or less. The molecular weight ratio (Mw / Mn) of the amorphous polyester resin is preferably from 1.0 to 4.0, more preferably from 1.0 to 3.5. The weight average molecular weight and number average molecular weight can be measured, for example, by gel permeation chromatography (GPC).
[0047] When the weight average molecular weight (Mw) of the amorphous polyester resin is less than 3,000 and the number average molecular weight (Mn) is less than 1,000, the toner may be inferior in heat resistance storage stability and durability against stress such as stirring in a developing machine. If the weight average molecular weight (Mw) of the amorphous polyester resin exceeds 10,000 and the number average molecular weight (Mn) exceeds 4,000, the viscoelasticity of the toner when melted increases, and low-temperature fixability may be deteriorated.
[0048] The content of the component having a molecular weight of 600 or less (THF soluble content) in the amorphous polyester resin is preferably 2% by mass or more and 10% by mass or less. If the content of the component having a molecular weight of 600 or less in the amorphous polyester resin exceeds 10% by mass, the toner may be deteriorated in heat-resistant storage stability and durability against stress such as stirring in a developing machine. If the content of the component having a molecular weight of 600 or less in the amorphous polyester resin is less than 2% by mass, the toner may have poor low-temperature fixability. As a method for adjusting the content of components having a molecular weight of 600 or less in the amorphous polyester resin, a method of extracting the amorphous polyester resin with methanol, removing components having a molecular weight of 600 or less, and purifying the resin can be given.
[0049] The acid value of the amorphous polyester resin is not particularly limited and may be appropriately selected depending on the purpose, but is preferably from 1 mgKOH / g to 50 mgKOH / g, more preferably from 5 mgKOH / g to 30 mgKOH / g. When the acid value is 1 mgKOH / g or more, the toner tends to be negatively charged, the affinity between the paper and the toner is improved when fixed onto the paper, and low-temperature fixability can be improved. When the acid value is 50 mgKOH / g or less, it is possible to prevent the problem of the charging stability, particularly the charging stability against environmental changes, decreasing.
[0050] The hydroxyl value of the amorphous polyester resin is not particularly limited and may be appropriately selected depending on the purpose, but is preferably 5 mgKOH / g or more.
[0051] The content of the amorphous polyester resin is preferably 60 parts by mass or more and 90 parts by mass or less with respect to 100 parts by mass of the toner, in that low-temperature fixability and heat-resistant storage stability can be achieved at the same time. When the content of the amorphous polyester resin is 60 parts by mass or more relative to 100 parts by mass of the toner, deformation due to heating and pressure during fixing is improved, and low-temperature fixing property is improved, which is preferable.When the content of the amorphous polyester resin is 90 parts by mass or less relative to 100 parts by mass of the toner, the crystalline polyester and the amorphous polyester are not uniformly compatible with each other, and the problem of poor low-temperature fixing property can be solved, which is preferable.
[0052] The glass transition temperature (Tg) of the amorphous polyester resin is preferably 40°C or more and 65°C or less, more preferably 45°C or more and 65°C or less, and even more preferably 50°C or more and 60°C or less. When the Tg of the amorphous polyester resin is 40° C. or higher, the heat-resistant storage stability of the toner and durability against stress such as stirring in a developing machine are improved, and the filming resistance is also improved. When the Tg of the amorphous polyester resin is 65° C. or less, deformation due to heat and pressure during toner fixing is improved, and low-temperature fixing properties are improved.
[0053] <<Modified polyester resin>> The modified polyester resin (hereinafter sometimes referred to as "modified polyester") is not particularly limited and can be appropriately selected depending on the purpose. For example, a reaction product of an active hydrogen group-containing compound and a polyester resin (in this specification, sometimes referred to as a "prepolymer" or "polyester prepolymer") having a site capable of reacting with the active hydrogen group-containing compound can be mentioned. The modified polyester resin is a polyester resin insoluble in tetrahydrofuran (THF). The polyester resin component insoluble in tetrahydrofuran (THF) lowers the glass transition temperature (Tg) and melt viscosity, and ensures low-temperature fixability, while having a branched structure in the molecular skeleton and a three-dimensional network structure in the molecular chain, and thus has rubber-like properties in that it deforms at low temperatures but does not flow.
[0054] The modified polyester resin has an active hydrogen group-containing compound and a site capable of reacting with the active hydrogen group-containing compound. The active hydrogen group is not particularly limited and can be appropriately selected depending on the purpose. Examples of the active hydrogen group include a hydroxyl group (an alcoholic hydroxyl group and a phenolic hydroxyl group), an amino group, a carboxyl group, and a mercapto group. These may be used alone or in combination of two or more.
[0055] -Active hydrogen group-containing compounds- The active hydrogen group-containing compound is not particularly limited and can be appropriately selected depending on the purpose. However, when the polyester resin having a site capable of reacting with the active hydrogen group-containing compound is a polyester resin containing an isocyanate group, amines are preferred in that the polyester resin can be polymerized by an elongation reaction, a crosslinking reaction, or the like with the polyester resin.
[0056] --Amines-- The amines are not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include diamines, trivalent or higher amines, amino alcohols, amino mercaptans, amino acids, blocked amino groups of these, etc. Among these, diamines and mixtures of diamines and small amounts of trivalent or higher amines are preferred. These may be used alone or in combination of two or more.
[0057] ---Diamine--- The diamine is not particularly limited and can be appropriately selected depending on the purpose. Examples of the diamine include aromatic diamines, alicyclic diamines, and aliphatic diamines. These may be used alone or in combination of two or more.
[0058] The aromatic diamine is not particularly limited and can be appropriately selected depending on the purpose. Examples of the aromatic diamine include phenylenediamine, diethyltoluenediamine, and 4,4'-diaminodiphenylmethane. These may be used alone or in combination of two or more.
[0059] The alicyclic diamine is not particularly limited and can be appropriately selected depending on the purpose. Examples of the alicyclic diamine include 4,4'-diamino-3,3'-dimethyldicyclohexylmethane, diaminocyclohexane, and isophoronediamine. These may be used alone or in combination of two or more.
[0060] The aliphatic diamine is not particularly limited and can be appropriately selected depending on the purpose. Examples of the aliphatic diamine include ethylenediamine, tetramethylenediamine, and hexamethylenediamine. These may be used alone or in combination of two or more.
[0061] ---Trivalent or higher amines--- The trivalent or higher amine is not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include diethylenetriamine and triethylenetetramine. These may be used alone or in combination of two or more.
[0062] ---Amino alcohol--- The amino alcohol is not particularly limited and can be appropriately selected depending on the purpose. Examples of the amino alcohol include ethanolamine and hydroxyethylaniline. These may be used alone or in combination of two or more.
[0063] ---Aminomercaptan--- The amino mercaptan is not particularly limited and can be appropriately selected depending on the purpose. Examples of the amino mercaptan include aminoethyl mercaptan and aminopropyl mercaptan. These may be used alone or in combination of two or more.
[0064] ---amino acid--- The amino acid is not particularly limited and can be appropriately selected depending on the purpose. Examples of the amino acid include aminopropionic acid and aminocaproic acid. These may be used alone or in combination of two or more.
[0065] --- Blocked amino groups --- The blocked amino group is not particularly limited and can be appropriately selected depending on the purpose. Examples of the blocked amino group include ketimine compounds and oxazoline compounds obtained by blocking the amino group with ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone. These may be used alone or in combination of two or more.
[0066] -Polyester resin having a site capable of reacting with an active hydrogen group-containing compound- The polyester resin having a site capable of reacting with the active hydrogen group-containing compound is not particularly limited and can be appropriately selected depending on the purpose. Examples of the polyester resin include a polyester resin containing an isocyanate group (hereinafter, sometimes referred to as a "polyester prepolymer having an isocyanate group").
[0067] --Polyester resin containing isocyanate groups-- The polyester resin containing an isocyanate group is not particularly limited and can be appropriately selected depending on the purpose. For example, a reaction product of a polyester resin having an active hydrogen group obtained by condensation polymerization of a polyol and a polycarboxylic acid and a polyisocyanate can be mentioned. These may be used alone or in combination of two or more.
[0068] ---Polyol--- The polyol is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include diols, trihydric or higher alcohols, mixtures of diols and trihydric or higher alcohols, etc. Among these, diols and mixtures of diols and a small amount of trihydric or higher alcohols are preferred. These may be used alone or in combination of two or more.
[0069] The modified polyester resin preferably contains a diol component. The diol is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include linear alkylene glycols, diols having an oxyalkylene group, alicyclic diols, bisphenols, alkylene oxide adducts of alicyclic diols, alkylene oxide adducts of bisphenols, etc. Among these, those having an odd carbon number of 3 to 9 in the main chain and having an alkyl group in the side chain are preferred.
[0070] The chain alkylene glycol is not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, and 1,6-hexanediol. These may be used alone or in combination of two or more. The number of carbon atoms of the chain alkylene glycol is not particularly limited and may be appropriately selected depending on the purpose, but is preferably from 2 to 12. Among these, at least one of a chain alkylene glycol having from 2 to 12 carbon atoms and an alkylene oxide adduct of a bisphenol is preferred, and an alkylene oxide adduct of a bisphenol or a mixture of an alkylene oxide adduct of a bisphenol and a chain alkylene glycol having from 2 to 12 carbon atoms is more preferred.
[0071] The diol having an oxyalkylene group is not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include diethylene glycol, triethylene glycol, dipropylene glycol, polyethylene glycol, polypropylene glycol, and polytetramethylene glycol. These may be used alone or in combination of two or more.
[0072] The alicyclic diol is not particularly limited and can be appropriately selected depending on the purpose. Examples of the alicyclic diol include 1,4-cyclohexanedimethanol and hydrogenated bisphenol A. These may be used alone or in combination of two or more.
[0073] The bisphenols are not particularly limited and can be appropriately selected depending on the purpose. Examples of the bisphenols include bisphenol A, bisphenol F, and bisphenol S. These may be used alone or in combination of two or more.
[0074] The alkylene oxide is not particularly limited and can be appropriately selected depending on the purpose. Examples of the alkylene oxide include ethylene oxide, propylene oxide, and butylene oxide. These may be used alone or in combination of two or more.
[0075] The trihydric or higher alcohol is not particularly limited and can be appropriately selected depending on the purpose. Examples of the trihydric or higher alcohol include aliphatic trihydric or higher alcohols, trihydric or higher polyphenols, and alkylene oxide adducts of trihydric or higher polyphenols. These may be used alone or in combination of two or more.
[0076] The trihydric or higher aliphatic alcohol is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, sorbitol, etc. Among these, the modified polyester resin preferably contains a trihydric or tetrahydric aliphatic polyhydric alcohol component having 3 to 10 carbon atoms. These may be used alone or in combination of two or more.
[0077] The trivalent or higher polyphenols are not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include trisphenol PA, phenol novolac, and cresol novolac. These may be used alone or in combination of two or more.
[0078] Examples of the alkylene oxide adducts of trivalent or higher polyphenols include those obtained by adding alkylene oxides such as ethylene oxide, propylene oxide, and butylene oxide to trivalent or higher polyphenols. These may be used alone or in combination of two or more.
[0079] When the diol and the trihydric or higher alcohol are used in combination, the mass ratio of the trihydric or higher alcohol to the diol (trihydric or higher alcohol / diol) is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.01 mass % or more and 10 mass % or less, and more preferably 0.01 mass % or more and 1 mass % or less.
[0080] ---Polycarboxylic acids--- The polycarboxylic acid is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include dicarboxylic acids, tri- or higher carboxylic acids, mixtures of dicarboxylic acids and tri- or higher carboxylic acids, etc. Among these, dicarboxylic acids and mixtures of dicarboxylic acids and tri- or higher carboxylic acids are preferred. These may be used alone or in combination of two or more.
[0081] The dicarboxylic acid is not particularly limited and can be appropriately selected depending on the purpose. Examples of the dicarboxylic acid include divalent alkanoic acids, divalent alkenoic acids, and aromatic dicarboxylic acids. These may be used alone or in combination of two or more.
[0082] The divalent alkanoic acid is not particularly limited and can be appropriately selected depending on the purpose. Examples of the divalent alkanoic acid include succinic acid, adipic acid, and sebacic acid. These may be used alone or in combination of two or more.
[0083] The divalent alkenoic acid is not particularly limited and can be appropriately selected depending on the purpose, but is preferably a divalent alkenoic acid having 4 to 20 carbon atoms. The divalent alkenoic acid having 4 to 20 carbon atoms is not particularly limited and can be appropriately selected depending on the purpose. Examples of the divalent alkenoic acid include maleic acid and fumaric acid. These may be used alone or in combination of two or more.
[0084] The aromatic dicarboxylic acid is not particularly limited and can be appropriately selected depending on the purpose, but is preferably an aromatic dicarboxylic acid having 8 to 20 carbon atoms. The aromatic dicarboxylic acid having 8 to 20 carbon atoms is not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include phthalic acid, isophthalic acid, terephthalic acid, and naphthalenedicarboxylic acid. These may be used alone or in combination of two or more.
[0085] The tri- or higher carboxylic acid is not particularly limited and can be appropriately selected depending on the purpose. Examples of the tri- or higher carboxylic acid include aromatic tri- or higher carboxylic acids. The trivalent or higher aromatic carboxylic acid is not particularly limited and may be appropriately selected depending on the purpose, but is preferably a trivalent or higher aromatic carboxylic acid having 9 to 20 carbon atoms. The trivalent or higher aromatic carboxylic acid having 9 to 20 carbon atoms is not particularly limited and can be appropriately selected depending on the purpose. Examples of the trivalent or higher aromatic carboxylic acid include trimellitic acid and pyromellitic acid. These may be used alone or in combination of two or more.
[0086] As the polycarboxylic acid, an acid anhydride or a lower alkyl ester of any of a dicarboxylic acid, a tri- or higher carboxylic acid, and a mixture of a dicarboxylic acid and a tri- or higher carboxylic acid can also be used. These may be used alone or in combination of two or more. The lower alkyl ester is not particularly limited and can be appropriately selected depending on the purpose. Examples of the lower alkyl ester include methyl ester, ethyl ester, and isopropyl ester. These may be used alone or in combination of two or more.
[0087] When the dicarboxylic acid and the tri- or higher carboxylic acid are used in combination, the mass ratio of the tri- or higher carboxylic acid to the dicarboxylic acid (tri- or higher carboxylic acid / dicarboxylic acid) is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.01% by mass or more and 10% by mass or less, and more preferably 0.01% by mass or more and 1% by mass or less.
[0088] When the polyol and the polycarboxylic acid are polycondensed, the equivalent ratio of the hydroxyl groups of the polyol to the carboxyl groups of the polycarboxylic acid (hydroxyl groups of the polyol / carboxyl groups of the polycarboxylic acid) is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 1 or more and 2 or less, more preferably 1 or more and 1.5 or less, and particularly preferably 1.02 or more and 1.3 or less.
[0089] The content of the polyol-derived structural units in the polyester prepolymer having an isocyanate group is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.5% by mass or more and 40% by mass or less, more preferably 1% by mass or more and 30% by mass or less, and even more preferably 2% by mass or more and 20% by mass or less. If the content of the polyol-derived structural unit in the polyester prepolymer having an isocyanate group is less than 0.5% by mass, the high-temperature offset resistance is reduced, and it may be difficult to achieve both the heat-resistant storage stability and the low-temperature fixability of the toner. If the content of the polyol-derived structural unit in the polyester prepolymer having an isocyanate group is more than 40% by mass, the low-temperature fixability may be reduced.
[0090] --Polyisocyanate-- The polyisocyanate is not particularly limited and can be appropriately selected depending on the purpose. Examples of the polyisocyanate include aliphatic diisocyanates, alicyclic diisocyanates, aromatic diisocyanates, araliphatic diisocyanates, isocyanurates, and those blocked with phenol derivatives, oximes, caprolactam, etc.
[0091] The aliphatic diisocyanate is not particularly limited and can be appropriately selected depending on the purpose. Examples of the aliphatic diisocyanate include tetramethylene diisocyanate, hexamethylene diisocyanate, methyl 2,6-diisocyanatocaproate, octamethylene diisocyanate, decamethylene diisocyanate, dodecamethylene diisocyanate, tetradecamethylene diisocyanate, trimethylhexane diisocyanate, and tetramethylhexane diisocyanate. These may be used alone or in combination of two or more.
[0092] The alicyclic diisocyanate is not particularly limited and can be appropriately selected depending on the purpose. Examples of the alicyclic diisocyanate include isophorone diisocyanate and cyclohexylmethane diisocyanate. These may be used alone or in combination of two or more.
[0093] The aromatic diisocyanate is not particularly limited and can be appropriately selected depending on the purpose. Examples of the aromatic diisocyanate include tolylene diisocyanate, diisocyanatodiphenylmethane, 1,5-naphthylene diisocyanate, 4,4'-diisocyanatodiphenyl, 4,4'-diisocyanato-3,3'-dimethyldiphenyl, 4,4'-diisocyanato-3-methyldiphenylmethane, and 4,4'-diisocyanato-diphenyl ether. These may be used alone or in combination of two or more.
[0094] The aromatic aliphatic diisocyanate is not particularly limited and may be appropriately selected depending on the purpose. For example, α,α,α',α'-tetramethylxylylene diisocyanate is exemplified.
[0095] The isocyanurates are not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include tris(isocyanatoalkyl)isocyanurate, tris(isocyanatocycloalkyl)isocyanurate, and the like. These may be used alone or in combination of two or more.
[0096] When the polyisocyanate is reacted with a polyester resin having a hydroxyl group, the equivalent ratio (NCO / OH) of the isocyanate group of the polyisocyanate to the hydroxyl group of the polyester resin is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 1 or more and 5 or less, more preferably 1.2 or more and 4 or less, and even more preferably 1.5 or more and 2.5 or less. When the polyisocyanate is reacted with a polyester resin having a hydroxyl group, if the equivalent ratio (NCO / OH) of the isocyanate group of the polyisocyanate to the hydroxyl group of the polyester resin is less than 1, the hot offset resistance may decrease. When the polyisocyanate is reacted with a polyester resin having a hydroxyl group, if the equivalent ratio (NCO / OH) of the isocyanate group of the polyisocyanate to the hydroxyl group of the polyester resin exceeds 5, the low-temperature fixability may decrease.
[0097] The content of the polyisocyanate-derived structural units in the polyester prepolymer having an isocyanate group is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.5% by mass or more and 40% by mass or less, more preferably 1% by mass or more and 30% by mass or less, and even more preferably 2% by mass or more and 20% by mass or less. When the content of the polyisocyanate-derived constitutional unit in the polyester prepolymer having an isocyanate group is less than 0.5% by mass, the high-temperature offset resistance may decrease. If the content of the structural unit derived from polyisocyanate in the polyester prepolymer having an isocyanate group exceeds 40% by mass, the low-temperature fixability may decrease.
[0098] The average number of isocyanate groups per molecule of the polyester prepolymer having an isocyanate group is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 1 or more, more preferably 1.5 to 3, and even more preferably 1.8 to 2.5. If the average number of isocyanate groups per molecule of the polyester prepolymer having an isocyanate group is less than 1, the molecular weight of the modified polyester resin becomes low, and the high-temperature offset resistance may decrease.
[0099] The modified polyester resin can be produced by a one-shot method, etc. As an example, a method for producing a urea-modified polyester resin will be described. First, a polyol and a polycarboxylic acid are heated to 150° C. or higher and 280° C. or lower in the presence of a catalyst such as tetrabutoxytitanate or dibutyltin oxide, and the water generated is removed, if necessary, under reduced pressure, to obtain a polyester resin having hydroxyl groups. Next, the polyester resin having a hydroxyl group is reacted with a polyisocyanate at 40° C. or higher and 140° C. or lower to obtain a polyester prepolymer having an isocyanate group. Furthermore, a polyester prepolymer having an isocyanate group is reacted with amines at 0° C. or higher and 140° C. or lower to obtain a urea-modified polyester resin.
[0100] When a polyester resin having a hydroxyl group is reacted with a polyisocyanate, and when a polyester prepolymer having an isocyanate group is reacted with an amine, a solvent can be used as necessary. The solvent is not particularly limited and can be appropriately selected depending on the purpose. Examples of the solvent include aromatic solvents, ketones, esters, amides, ethers, and other solvents that are inactive to isocyanate groups. Examples of the aromatic solvent include toluene and xylene. Examples of the ketones include acetone, methyl ethyl ketone, and methyl isobutyl ketone. The esters include, for example, ethyl acetate. Examples of the amides include dimethylformamide and dimethylacetamide. The ethers include, for example, tetrahydrofuran. These may be used alone or in combination of two or more.
[0101] The modified polyester resin preferably has at least one of a urethane bond and a urea bond in the branched structure portion, since the urethane bond or the urea bond behaves like a pseudo-crosslinking point, the modified polyester resin has stronger rubber-like properties, and a toner having excellent heat-resistant storage stability and high-temperature offset resistance can be produced.
[0102] The structure of the modified polyester resin is not particularly limited and may be appropriately selected depending on the purpose. Examples of the structure include those shown in the following structural formulas (1) to (3). R1-(NHCONH-R2)n- Formula (1) R1-(NHCOO-R2)n- Formula (2) R1-(OCONH-R2)n- Formula (3) (In the above formula, n=3, R1 represents an isocyanurate skeleton, and R2 represents a group derived from any one of a polyester resin containing a polycarboxylic acid and a polyol, and a modified polyester resin obtained by modifying a polyester with an isocyanate.)
[0103] The method for bonding R1 and R2 in the formulas (1) to (3) is not particularly limited and can be appropriately selected depending on the purpose. For example, there are the following methods (a) and (b). (a) A method in which a diol component and a dicarboxylic acid component are subjected to an esterification reaction to produce a polyester polyol (R2) having hydroxyl groups at the terminals, and the resulting polyester polyol is reacted with an isocyanurate (R1). (b) A method in which a diol component and a dicarboxylic acid component are subjected to an ester reaction to produce a polyester polyol (R2) having hydroxyl groups at the terminals, the resulting polyester polyol is reacted with a divalent polyisocyanate to produce an isocyanate-modified polyester (R2), and the resulting isocyanate-modified polyester is reacted with an isocyanurate (R1) in the presence of pure water. It is also possible to further react the hydroxyl groups remaining in the polyol obtained by either of (a) or (b) with a divalent or higher polyisocyanate to form a polyester prepolymer, which can then be reacted with a curing agent in the toner production process for use.
[0104] In the toner production process, the reaction with the curing agent produces urethane or urea bonds, which behave like strong crosslinking points, and the rubber-like properties of the modified polyester resin are enhanced, resulting in excellent heat resistance storage stability and high-temperature offset resistance. Therefore, R2 in the formulas (1) to (3) is preferably a modified polyester resin modified with isocyanate.
[0105] The curing agent is not particularly limited as long as it is a curing agent that can react with a polyester prepolymer (a reaction product of the polyester portion of R2 and the polyisocyanate, i.e., a reaction precursor to be reacted with a curing agent) to produce the polyester resin, and can be appropriately selected depending on the purpose. For example, an active hydrogen group-containing compound can be used.
[0106] The glass transition temperature (Tg) of the modified polyester resin is not particularly limited, but is preferably from -60°C to 0°C, and more preferably from -40°C to -20°C. If the Tg of the modified polyester resin is -60°C or higher, the flow of the toner at low temperatures cannot be suppressed, and the problems of deterioration of the heat-resistant storage stability and deterioration of the filming resistance can be prevented. When the Tg of the modified polyester resin is 0° C. or lower, the toner cannot be sufficiently deformed by the application of heat and pressure during fixing, and the problem of insufficient low-temperature fixing property can be prevented.
[0107] The content of the modified polyester resin is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 1 part by mass or more and 15 parts by mass or less, and more preferably 5 parts by mass or more and 10 parts by mass or less, relative to 100 parts by mass of the toner.
[0108] The molecular structures of the amorphous polyester resin and the modified polyester resin can be confirmed by NMR measurement of a solution or solid, as well as X-ray diffraction, GC / MS, LC / MS, IR measurement, and the like. In the infrared absorption spectrum, the -1 and 990±10cm -1 One method is to detect a resin that does not have absorption due to olefin δCH (out-of-plane bending vibration) as an amorphous polyester resin.
[0109] The number average molecular weight (Mn) of the modified polyester resin is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 1,000 to 10,000, more preferably 1,500 to 6,000, as measured by GPC (gel permeation chromatography).
[0110] The weight average molecular weight of the modified polyester resin is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 20,000 or more and 1,000,000 or less as measured by GPC (gel permeation chromatography). When the weight average molecular weight of the modified polyester resin is 20,000 or more, the toner becomes easily fluid at low temperatures, which prevents the problems of poor heat-resistant storage stability and low viscosity when melted, which prevents the problems of reduced high-temperature offset resistance.
[0111] <Coloring agent> The toner of the present invention contains a colorant. The colorant is not particularly limited and can be appropriately selected depending on the purpose. Examples of the colorant include carbon black, nigrosine dye, iron black, naphthol yellow S, Hansa yellow (10G, 5G, G), cadmium yellow, yellow iron oxide, yellow ocher, yellow lead, titanium yellow, polyazo yellow, oil yellow, Hansa yellow (GR, A, RN, R), pigment yellow L, benzidine yellow (G, GR), permanent yellow (NCG), Balkan fast yellow (5G, R), tartrazine lake, quinoline yellow lake, and anthrazan yellow BG. L, Isoindolinone Yellow, Bengala, Red Lead, Cinnabar, Cadmium Red, Cadmium Mercury Red, Antimony Vermilion, Permanent Red 4R, Para Red, Phaysee Red, Parachlor Orthonitroaniline Red, Lithol Fast Scarlet G, Brilliant Fast Scarlet, Brilliant Carmine BS, Permanent Red (F2R, F4R, FRL, FRLL, F4RH), Fast Scarlet VD, Belkan Fast Rubin B, Brilliant Scarlet G, Lithol Rubin GX, Permanent Red F5R, Brilliant Carmine 6B, Pigment Scarlet 3B, Bordeaux 5B, Toluidine Maroon, Permanent Bordeaux F2K, Helio Bordeaux BL, Bordeaux 10B, Bon Maroon Light, Bon Maroon Medium, Eosin Lake, Rhodamine Lake B, Rhodamine Lake Y, Alizarin Lake, Thioindigo Red B, Thioindigo Maroon, Oil Red, Quinacridone Red, Pyrazolone Red, Polyazo Red, Chrome Vermilion, Benzidine Orange, Perinone Orange, Oil Orange, Cobalt Blue, Cerulean Blue, Alkaline Blue Lake, Peacock Blue Lake, Victoria Blue Lake, Metal-free Phthalocyanine Blue, Phthalocyanine Blue, Fast Sky Blue, Indanthrene Blue (RS, BC), Indigo, Ultramarine Blue, Prussian Blue, Anthraquinone Blue, Fast Violet B, Methyl Violet Lake, Cobalt Purple, Manganese Purple, Dioxane Violet, Anthraquinone Violet, Chrome Green, Zinc Green, Chromium Oxide, Pyridian, Emerald Green, Pigment Green B, Naphthol Green B, Green Gold, Acid Green Lake,Examples include malachite green lake, phthalocyanine green, anthraquinone green, titanium oxide, zinc oxide, and lithopone. These may be used alone or in combination of two or more.
[0112] The content of the colorant is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 1 part by mass or more and 15 parts by mass or less, and more preferably 3 parts by mass or more and 10 parts by mass or less, relative to 100 parts by mass of the toner.
[0113] The colorant may also be used as a master batch in which it is combined with a resin. Examples of the resin contained in the master batch include polymers of styrene or its substitutes, such as polystyrene, poly-p-chlorostyrene, and polyvinyltoluene: styrene-p-chlorostyrene copolymer, styrene-propylene copolymer, styrene-vinyltoluene copolymer, styrene-vinylnaphthalene copolymer, styrene-methyl acrylate copolymer, styrene-ethyl acrylate copolymer, styrene-butyl acrylate copolymer, styrene-octyl acrylate copolymer, styrene-methyl methacrylate copolymer, styrene-ethyl methacrylate copolymer, styrene-butyl methacrylate copolymer, styrene-α-chloromethyl methacrylate copolymer, and styrene-acrylonitrile. styrene-based copolymers such as styrene-vinyl methyl ketone copolymers, styrene-butadiene copolymers, styrene-isoprene copolymers, styrene-acrylonitrile-indene copolymers, styrene-maleic acid copolymers, and styrene-maleic acid ester copolymers; polymethyl methacrylate, polybutyl methacrylate, polyvinyl chloride, polyvinyl acetate, polyethylene, polypropylene, polyester, epoxy resins, epoxy polyol resins, polyurethane, polyamide, polyvinyl butyral, polyacrylic acid resins, rosin, modified rosin, terpene resins, aliphatic or alicyclic hydrocarbon resins, aromatic petroleum resins, chlorinated paraffin, and paraffin wax. These may be used alone or in combination of two or more.
[0114] The master batch can be obtained by mixing and kneading the resin for the master batch and the colorant under high shear force. In this case, an organic solvent can be used to enhance the interaction between the colorant and the resin for the master batch. In addition, the so-called flushing method, in which an aqueous paste containing water of the colorant is mixed and kneaded with the resin for the master batch and the organic solvent, the colorant is transferred to the resin side, and the moisture and organic solvent components are removed, is preferably used because the wet cake of the colorant can be used as it is and there is no need to dry it. When mixing and kneading, a high shear dispersing device such as a three-roll mill is preferably used.
[0115] <Release agent> The toner of the present invention contains a release agent. The releasing agent is not particularly limited and can be appropriately selected from known agents, such as waxes. Examples of the waxes include natural waxes such as vegetable waxes such as carnauba wax, cotton wax, and wood wax; animal waxes such as beeswax and lanolin; mineral waxes such as ozokerite and cerusin; and petroleum waxes such as paraffin, microcrystalline, and petrolatum. In addition to these natural waxes, synthetic hydrocarbon waxes such as Fischer-Tropsch wax, polyethylene, and polypropylene; and synthetic waxes such as esters, ketones, and ethers may also be used. Furthermore, fatty acid amide compounds such as 12-hydroxystearic acid amide, stearic acid amide, phthalimide anhydride, and chlorinated hydrocarbons; homopolymers or copolymers of polyacrylates such as poly-n-stearyl methacrylate and poly-n-lauryl methacrylate, which are low molecular weight crystalline polymer resins (for example, copolymers of n-stearyl acrylate and ethyl methacrylate); and crystalline polymers having long alkyl groups in their side chains may be used. Among these, hydrocarbon waxes such as paraffin wax, microcrystalline wax, Fischer-Tropsch wax, polyethylene wax, and polypropylene wax are preferred. These may be used alone or in combination of two or more.
[0116] The melting point of the release agent is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 60° C. or higher and 80° C. or lower. If the melting point of the release agent is lower than 60° C., the release agent tends to melt at low temperatures, and the heat-resistant storage stability may be deteriorated. If the melting point of the release agent exceeds 80° C., even if the resin is melted and within the fixing temperature range, the release agent may not melt sufficiently, causing fixing offset and resulting in defects in the image.
[0117] The content of the release agent is not particularly limited and can be appropriately selected depending on the purpose. From the viewpoint of improving image quality and excellent low-temperature fixing property, the content is preferably 2 parts by mass or more and 10 parts by mass or less, and more preferably 3 parts by mass or more and 8 parts by mass or less, relative to 100 parts by mass of the toner. If the content of the releasing agent is less than 2 parts by mass, the high-temperature offset resistance during fixing and the low-temperature fixing property may be deteriorated. If the content of the release agent exceeds 10 parts by mass, the heat-resistant storage stability may decrease and image fogging may easily occur.
[0118] <Amorphous hybrid resin> The toner of the present invention preferably contains an amorphous hybrid resin. The hybrid resin means a composite resin in which different types of resins are bonded together. The toner of the present invention preferably contains at least one amorphous hybrid resin containing a condensation polymerization resin and an addition polymerization resin. It is also preferred that the condensation polymerization resin and the addition polymerization resin in the amorphous hybrid resin are partially chemically bonded, and that at least one of the condensation polymerization resin and the addition polymerization resin is made of a resin component of the same polymerization system as the polyester resin. By doing so, it is possible to control the exposure of the crystalline polyester resin to the surface of the toner base particle and to improve the dispersibility of the crystalline polyester resin inside the toner base particle, thereby contributing to achieving both low-temperature fixability and heat-resistant storage stability.
[0119] The amorphous hybrid resin can be obtained by reacting a mixture of raw material monomers for the condensation polymerization resin and the addition polymerization resin. The amorphous hybrid resin is preferably a resin obtained by mixing the mixture with a dual-reactive monomer that is a monomer capable of reacting with both of the raw material monomers of the condensation polymerization resin and the addition polymerization resin.
[0120] - Raw material monomer for condensation polymerization resins - The raw material monomers for the condensation polymerization resin are not particularly limited and can be appropriately selected depending on the purpose, but succinic acid derivatives and the like are preferred as the carboxylic acid component.
[0121] - Raw material monomer for addition polymerization resins - The raw material monomer of the addition polymerization resin is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include styrene derivatives such as styrene, α-methylstyrene, vinyltoluene, etc.; (meth)acrylic acid alkyl esters; ethylenically unsaturated monoolefins such as ethylene and propylene; diolefins such as butadiene; halovinyls such as vinyl chloride; vinyl esters such as vinyl acetate and vinyl propionate; ethylenically monocarboxylic acid esters such as dimethylaminoethyl (meth)acrylate; vinyl ethers such as vinyl methyl ether; vinylidene halides such as vinylidene chloride; and N-vinyl compounds such as N-vinylpyrrolidone. Among these, styrene derivatives such as styrene, α-methylstyrene, vinyltoluene, etc. are preferred. In addition, in terms of low-temperature fixing property and charging stability, (meth)acrylic acid alkyl esters are preferred. These may be used alone or in combination of two or more.
[0122] --(Meth)acrylic acid alkyl ester-- From the viewpoints of low-temperature fixability and charging stability, the number of carbon atoms in the alkyl group in the (meth)acrylic acid alkyl ester is preferably from 1 to 22, and more preferably from 8 to 18. The number of carbon atoms in the (meth)acrylic acid alkyl ester refers to the number of carbon atoms derived from the alcohol component constituting the ester. Specific examples of the (meth)acrylic acid alkyl ester include methyl (meth)acrylate, ethyl (meth)acrylate, (iso)propyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, (iso)butyl (meth)acrylate, (tertiary)butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, (iso)octyl (meth)acrylate, (iso)decyl (meth)acrylate, and (iso)stearyl (meth)acrylate. These may be used alone or in combination of two or more.
[0123] From the viewpoints of low-temperature fixing property, heat-resistant storage stability, and charging stability of the toner, the content of the (meth)acrylic acid alkyl ester is preferably 50% by mass or less, more preferably 30% by mass or less, and even more preferably 20% by mass or less, based on the total mass of the raw material monomers of the addition polymerization resin.
[0124] -Ambi-reactive monomer- The bireactive monomer is not particularly limited and can be appropriately selected depending on the purpose. From the viewpoint of improving the dispersibility of the resin that becomes the dispersed phase, however, it is preferable that the bireactive monomer is a monomer having at least one functional group selected from the group consisting of a hydroxyl group, a carboxyl group, an epoxy group, a primary amino group, and a secondary amino group, and an ethylenically unsaturated bond in the molecule. Specific examples of the bireactive monomer include acrylic acid, fumaric acid, methacrylic acid, citraconic acid, maleic acid, etc. Among these, acrylic acid, methacrylic acid and fumaric acid are preferred. These may be used alone or in combination of two or more.
[0125] The content of the bireactive monomer is preferably 0.1 parts by mass or more and 10 parts by mass or less based on 100 parts by mass of the raw material monomer of the condensation polymerization resin. In the present invention, the bireactive monomer is a monomer different from the raw material monomers for the condensation polymerization resin and the raw material monomers for the addition polymerization resin because of the specificity of its performance.
[0126] When the amorphous hybrid resin is obtained by carrying out a polymerization reaction using a mixture of raw material monomers of the condensation polymerization resin and the addition polymerization resin, and the bireactive monomer, the polymerization reaction does not need to proceed and be completed simultaneously in terms of time, and the polymerization reaction may be allowed to proceed and be completed by appropriately selecting a reaction temperature and time according to the respective reaction mechanisms. For example, in the method for producing the amorphous hybrid resin of the present invention, it is preferable to mix raw material monomers for a condensation polymerization resin, raw material monomers for an addition polymerization resin, a bireactive monomer, a catalyst such as a polymerization initiator, and the like, and then obtain an addition polymerization resin component having a functional group capable of undergoing a condensation polymerization reaction by a radical polymerization reaction at 50° C. or higher and 180° C. or lower, and then increase the reaction temperature to 190° C. or higher and 270° C. or lower to form a condensation polymerization resin component by a condensation polymerization reaction.
[0127] The softening point of the amorphous hybrid resin is not particularly limited, but is preferably from 80°C to 170°C, more preferably from 90°C to 160°C, and even more preferably from 95°C to 155°C.
[0128] The content of the amorphous hybrid resin is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 15% by mass or more based on the total mass of the crystalline polyester resin. If the content of the amorphous hybrid resin is less than 15% by mass, the dispersibility of the crystalline polyester resin inside the toner decreases, and the crystalline polyester resin is excessively disposed on the surface of the toner, which may deteriorate the heat-resistant storage stability.
[0129] <Other Ingredient A> The other component A is not particularly limited as long as it is used in a normal toner, and can be appropriately selected depending on the purpose. Examples of the other component A include binder resins other than the polyester resins (the crystalline polyester resin, the amorphous polyester resin, and the modified polyester resin), charge control agents, external additives, flowability improvers, cleaning property improvers, magnetic materials, and the like.
[0130] -Binder resins other than polyester resins- In the present invention, the polyester resin refers to the crystalline polyester resin, the amorphous polyester resin, and the modified polyester resin. The binder resin other than the polyester resin is not particularly limited and may be appropriately selected depending on the purpose, and examples thereof include styrene acrylic resin, polyol resin, vinyl resin, polyurethane resin, epoxy resin, polyamide resin, polyimide resin, silicon resin, phenol resin, melamine resin, urea resin, aniline resin, ionomer resin, polycarbonate resin, etc. Among these, polyester resin is preferable because it can impart flexibility to the toner. These may be used alone or in combination of two or more.
[0131] -Charge control agent- The charge control agent is not particularly limited and can be appropriately selected depending on the purpose. Examples of the charge control agent include nigrosine dyes, triphenylmethane dyes, chromium-containing metal complex dyes, molybdic acid chelate pigments, rhodamine dyes, alkoxy amines, quaternary ammonium salts (including fluorine-modified quaternary ammonium salts), alkylamides, phosphorus simple substance or compounds, tungsten simple substance or compounds, fluorine-based activators, metal salicylic acid salts, and metal salts of salicylic acid derivatives.
[0132] The content of the charge control agent is determined by the type of the binder resin, the presence or absence of external additives used as necessary, and the toner production method including the dispersion method, and is not uniquely limited. However, the content is preferably 0.1 parts by mass or more and 10 parts by mass or less, and more preferably 0.2 parts by mass or more and 5 parts by mass or less, relative to 100 parts by mass of the binder resin. If the content of the charge control agent exceeds 10 parts by mass with respect to 100 parts by mass of the binder resin, the chargeability of the toner becomes too high, which may reduce the effect of the main charge control agent and increase the electrostatic attraction force with the developing roller, resulting in a decrease in the fluidity of the developer and a decrease in image density. The charge control agent may be melt-kneaded together with the master batch and then dissolved and dispersed, or may be added when directly dissolving or dispersing in an organic solvent, or may be fixed on the toner surface after the toner particles are produced.
[0133] Examples of commercially available charge control agents include the nigrosine dye Bontron 03, the quaternary ammonium salt Bontron P-51, the metal-containing azo dye Bontron S-34, the oxynaphthoic acid metal complex E-82, the salicylic acid metal complex E-84, and the phenol condensate E-89 (all manufactured by Orient Chemical Industry Co., Ltd.), the quaternary ammonium salt molybdenum complexes TP-302 and TP-415 (all manufactured by Hodogaya Chemical Co., Ltd.), LRA-901, and the boron complex LR-147 (all manufactured by Nippon Carlit Co., Ltd.).
[0134] -External additives- The external additive is not particularly limited and can be appropriately selected depending on the purpose. Examples of the external additive include oxide fine particles and inorganic fine particles. Examples of the inorganic fine particles include silica, alumina, titanium oxide, barium titanate, magnesium titanate, calcium titanate, strontium titanate, iron oxide, copper oxide, zinc oxide, tin oxide, silica sand, clay, mica, wollastonite, diatomaceous earth, chromium oxide, cerium oxide, red iron oxide, antimony trioxide, magnesium oxide, zirconium oxide, barium sulfate, barium carbonate, calcium carbonate, silicon carbide, silicon nitride, etc. Among these, silica and titanium oxide are preferred. These may be used alone or in combination of two or more.
[0135] The average particle size of the primary particles of the inorganic fine particles is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 100 nm or less, and more preferably 3 nm to 70 nm. When the average particle size of the primary particles of the inorganic fine particles is 100 nm or less, the inorganic fine particles can be prevented from being buried in the toner, making it difficult to effectively exert their functions, and from being unevenly damaged on the photoreceptor surface.
[0136] The oxide fine particles and the inorganic fine particles are preferably subjected to a hydrophobic treatment or an oil treatment. The method for producing the hydrophobic treated fine particles is not particularly limited, and for example, they can be obtained by treating hydrophilic fine particles with a silane coupling agent such as methyltrimethoxysilane, methyltriethoxysilane, or octyltrimethoxysilane. The method for producing the oil-treated fine particles is not particularly limited, and the fine particles can be obtained, for example, by treating the fine particles with silicone oil or the like.
[0137] The silicone oil is not particularly limited and can be appropriately selected depending on the purpose. Examples of the silicone oil include dimethyl silicone oil, methyl phenyl silicone oil, chlorophenyl silicone oil, methyl hydrogen silicone oil, alkyl modified silicone oil, fluorine modified silicone oil, polyether modified silicone oil, alcohol modified silicone oil, amino modified silicone oil, epoxy modified silicone oil, epoxy / polyether modified silicone oil, phenol modified silicone oil, carboxyl modified silicone oil, mercapto modified silicone oil, methacryl modified silicone oil, and α-methylstyrene modified silicone oil. These may be used alone or in combination of two or more.
[0138] Specific examples of the external additive include silica fine particles, hydrophobic silica, fatty acid metal salts (e.g., zinc stearate, aluminum stearate, etc.), metal oxides (e.g., titania, alumina, tin oxide, antimony oxide, etc.), fluoropolymers, etc. Among these, hydrophobically treated silica fine particles, hydrophobically treated titania fine particles, hydrophobically treated titanium oxide fine particles, and hydrophobically treated alumina fine particles are preferred. These may be used alone or in combination of two or more.
[0139] The external additives may be appropriately synthesized or may be commercially available products. Commercially available products of the silica fine particles include, for example, R972, R974, RX200, RY200, R202, R805, and R812 (all manufactured by Nippon Aerosil Co., Ltd.). Commercially available examples of the titania oxide microparticles include P-25 (manufactured by Nippon Aerosil Co., Ltd.), STT-30, STT-65C-S (all manufactured by Titanium Kogyo Co., Ltd.), TAF-140 (manufactured by Fuji Titanium Kogyo Co., Ltd.), MT-150W, MT-500B, MT-600B, MT-150A (all manufactured by Teika Co., Ltd.), and the like. Commercially available examples of the titanium microparticles include T-805 (manufactured by Nippon Aerosil Co., Ltd.), STT-30A, STT-65S-S (all manufactured by Titanium Kogyo Co., Ltd.), TAF-500T, TAF-1500T (all manufactured by Fuji Titanium Kogyo Co., Ltd.), MT-100S, MT-100T (all manufactured by Teika Corporation), and IT-S (manufactured by Ishihara Sangyo Co., Ltd.).
[0140] The average particle size of the hydrophobized primary particles in the external additive is not particularly limited and may be appropriately selected depending on the purpose, but is preferably from 1 nm to 100 nm, more preferably from 5 nm to 70 nm. The external additive preferably contains at least one type of inorganic fine particles having an average primary particle size of 20 nm or less that has been hydrophobized, and at least one type of inorganic fine particles having an average primary particle size of 30 nm or more.
[0141] The specific surface area of the external additive by the BET method is 20 m 2 / g or more 500m 2 It is preferable that the molecular weight is not more than 1 / g.
[0142] The content of the external additive is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.1 parts by mass or more and 5 parts by mass or less, and more preferably 0.3 parts by mass or more and 3 parts by mass or less, relative to 100 parts by mass of the toner.
[0143] -Flow improver- The flowability improver is not particularly limited as long as it is capable of performing a surface treatment to increase hydrophobicity and prevent deterioration of flowability and charging properties even under high humidity conditions, and can be appropriately selected depending on the purpose. Examples of the flowability improver include silane coupling agents, silylating agents, silane coupling agents having a fluorinated alkyl group, organic titanate coupling agents, aluminum coupling agents, silicone oils, and modified silicone oils. These may be used alone or in combination of two or more. The silica and titanium oxide are preferably surface-treated with the flowability improving agent and used as hydrophobic silica and hydrophobic titanium oxide.
[0144] -Cleaning improver- The cleaning property improver is not particularly limited as long as it is added to the toner in order to remove the developer remaining on the photoconductor or the primary transfer medium after transfer, and may be appropriately selected depending on the purpose. Examples of the cleaning property improver include fatty acid metal salts such as zinc stearate, calcium stearate, and stearic acid, polymer fine particles produced by soap-free emulsion polymerization, such as polymethyl methacrylate fine particles and polystyrene fine particles. These may be used alone or in combination of two or more. The polymer fine particles preferably have a relatively narrow particle size distribution, and the volume average particle size is preferably from 0.01 μm to 1 μm.
[0145] -Magnetic materials- The magnetic material is not particularly limited and may be appropriately selected depending on the purpose, and examples thereof include iron powder, magnetite, ferrite, etc. Among these, those that are white in color are preferred. These may be used alone or in combination of two or more.
[0146] [Resin particles] In the present invention, resin particles are present on the surface of the toner base particles. The resin particles are preferably made by combining resin fine particles (A) made of two types of styrene-acrylic resins and resin fine particles (B) made of one type of styrene-acrylic resin.
[0147] <Resin fine particles (A)> The resin fine particles (A) can be obtained by homopolymerizing or copolymerizing a vinyl monomer. The resin fine particles (A) are preferably one or more types of styrene-acrylic resin having at least a carboxylic acid. The resin particles (A) preferably consist of two types of styrene-acrylic resins, (a1) and (a2), and more preferably have a core-shell structure with the styrene-acrylic resin (a1) as the shell and the styrene-acrylic resin (a2) as the core. Furthermore, the resin fine particles (A) may contain another component B, if necessary. Of the organic fine particles (A) containing vinyl units composed of the styrene-acrylic resin (a1) and the styrene-acrylic resin (a2), the styrene-acrylic resin (a2) is a polymer obtained by homopolymerizing or copolymerizing a vinyl monomer. In the present invention, the styrene-acrylic resin (a1) may be referred to as "resin (a1)" hereinafter. In the present invention, the styrene-acrylic resin (a2) may be referred to as "resin (a2)" hereinafter.
[0148] The vinyl monomer is not particularly limited and can be appropriately selected depending on the purpose. Examples thereof include (1) to (10) shown below. In addition, in the synthesis of the organic fine particles A, one of the vinyl monomers (1) to (10) shown below may be used alone, or two or more of them may be used in combination.
[0149] (1) Vinyl hydrocarbons The vinyl hydrocarbon is not particularly limited and can be appropriately selected depending on the purpose. Examples of the vinyl hydrocarbon include aliphatic vinyl hydrocarbons, alicyclic vinyl hydrocarbons, and aromatic vinyl hydrocarbons.
[0150] Examples of the aliphatic vinyl hydrocarbons include alkenes and alkadienes. Specific examples of the alkenes include ethylene, propylene, and α-olefins. Specific examples of the alkadienes include butadiene, isoprene, 1,4-pentadiene, 1,6-hexadiene, and 1,7-octadiene.
[0151] Examples of the alicyclic vinyl hydrocarbons include mono-cycloalkenes, di-cycloalkenes, alkadienes, and the like. Specific examples of the alicyclic vinyl hydrocarbon include (di)cyclopentadiene and terpene.
[0152] Examples of the aromatic vinyl hydrocarbons include styrene and its hydrocarbyl (alkyl, cycloalkyl, aralkyl and / or alkenyl) substituted products. Specific examples of the aromatic vinyl hydrocarbon include α-methylstyrene, 2,4-dimethylstyrene, and vinylnaphthalene.
[0153] (2) Carboxyl-containing vinyl monomers and their salts Examples of the carboxyl group-containing vinyl monomer and its salt include unsaturated monocarboxylic acids (salts) having 3 to 30 carbon atoms, unsaturated dicarboxylic acids (salts), and anhydrides (salts) thereof, as well as monoalkyl (having 1 to 24 carbon atoms) esters thereof or salts thereof.
[0154] Specific examples of the carboxyl group-containing vinyl monomer and salts thereof include carboxyl group-containing vinyl monomers such as (meth)acrylic acid, (anhydride) maleic acid, maleic acid monoalkyl esters, fumaric acid, fumaric acid monoalkyl esters, crotonic acid, itaconic acid, itaconic acid monoalkyl esters, itaconic acid glycol monoether, citraconic acid, citraconic acid monoalkyl esters, and cinnamic acid, as well as metal salts thereof. In the present invention, the term "(salt)" refers to an acid or a salt thereof. For example, an unsaturated monocarboxylic acid (salt) having 3 to 30 carbon atoms refers to an unsaturated monocarboxylic acid or a salt thereof. In the present invention, "(meth)acrylic" means methacrylic acid or acrylic acid. In the present invention, "(meth)acryloyl" means methacryloyl or acryloyl. In the present invention, "(meth)acrylate" means methacrylate or acrylate.
[0155] (3) Sulfonic acid-containing vinyl monomers, vinyl sulfate monoesters, and their salts Examples of the sulfone group-containing vinyl monomer, the vinyl sulfate monoester, and the salts thereof include alkene sulfonic acids (salts) having 2 to 14 carbon atoms, alkyl sulfonic acids (salts) having 2 to 24 carbon atoms, sulfo(hydroxy)alkyl-(meth)acrylates (salts) or (meth)acrylamides (salts), and alkylarylsulfosuccinic acids (salts). Examples of the alkene sulfonic acid (salt) having 2 to 14 carbon atoms include vinyl sulfonic acid (salt). Examples of the alkylsulfonic acid (salt) having 2 to 24 carbon atoms include α-methylstyrenesulfonic acid (salt). Examples of the sulfo(hydroxy)alkyl-(meth)acrylate (salt) or (meth)acrylamide (salt) include sulfopropyl(meth)acrylate (salt), sulfate ester (salt), and sulfonic acid group-containing vinyl monomer (salt).
[0156] (4) Phosphate-containing vinyl monomers and their salts Examples of the phosphoric acid group-containing vinyl monomer and its salt include (meth)acryloyloxyalkyl (carbon number 1 to 24) phosphoric acid monoester (salt), (meth)acryloyloxyalkyl (carbon number 1 to 24) phosphonic acid (salt), and the like. Specific examples of the (meth)acryloyloxyalkyl (carbon number 1 to 24) phosphate monoester (salt) include 2-hydroxyethyl (meth)acryloyl phosphate (salt), phenyl-2-acryloyloxyethyl phosphate (salt), and the like. Specific examples of (meth)acryloyloxyalkyl (carbon number 1 to 24)phosphonic acids (salts) include 2-acryloyloxyethylphosphonic acid (salts). Examples of the salts of (2) to (4) above include alkali metal salts (sodium salts, potassium salts, etc.), alkaline earth metal salts (calcium salts, magnesium salts, etc.), ammonium salts, amine salts, and quaternary ammonium salts.
[0157] (5) Hydroxyl-containing vinyl monomers Examples of the hydroxyl group-containing vinyl monomer include hydroxystyrene, N-methylol (meth)acrylamide, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, (meth)allyl alcohol, crotyl alcohol, isocrotyl alcohol, 1-buten-3-ol, 2-buten-1-ol, 2-butene-1,4-diol, propargyl alcohol, 2-hydroxyethyl propenyl ether, and sucrose allyl ether.
[0158] (6) Nitrogen-containing vinyl monomers Examples of the nitrogen-containing vinyl monomer include amino group-containing vinyl monomers, amide group-containing vinyl monomers, nitrile group-containing vinyl monomers, quaternary ammonium cation group-containing vinyl monomers, and nitro group-containing vinyl monomers.
[0159] The amino group-containing vinyl monomer may, for example, be aminoethyl (meth)acrylate.
[0160] Examples of the amide group-containing vinyl monomer include (meth)acrylamide and N-methyl(meth)acrylamide.
[0161] Examples of the amide group-containing vinyl monomer include (meth)acrylamide and N-methyl(meth)acrylamide.
[0162] Examples of the nitrile group-containing vinyl monomer include (meth)acrylonitrile, cyanostyrene, and cyanoacrylate.
[0163] Examples of the quaternary ammonium cation group-containing vinyl monomer include quaternized products of tertiary amine group-containing vinyl monomers such as dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylamide, diethylaminoethyl (meth)acrylamide, and diallylamine (which are quaternized using a quaternizing agent such as methyl chloride, dimethyl sulfate, benzyl chloride, or dimethyl carbonate).
[0164] The nitro group-containing vinyl monomer may, for example, be nitrostyrene.
[0165] (7) Epoxy group-containing vinyl monomer Examples of the epoxy group-containing vinyl monomer include glycidyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, and p-vinylphenyl phenyl oxide.
[0166] (8) Halogen-containing vinyl monomers Examples of the halogen-containing vinyl monomer include vinyl chloride, vinyl bromide, vinylidene chloride, allyl chloride, chlorostyrene, bromostyrene, dichlorostyrene, chloromethylstyrene, tetrafluorostyrene, and chloroprene.
[0167] (9) Vinyl esters, vinyl (thio)ethers, vinyl ketones Examples of the vinyl ester include vinyl acetate, vinyl butyrate, vinyl propionate, vinyl butyrate, diallyl phthalate, diallyl adipate, isopropenyl acetate, vinyl methacrylate, methyl 4-vinyl benzoate, cyclohexyl methacrylate, benzyl methacrylate, phenyl (meth)acrylate, vinyl methoxyacetate, vinyl benzoate, ethyl α-ethoxyacrylate, alkyl (meth)acrylates having an alkyl group with 1 to 50 carbon atoms, dialkyl fumarate (the two alkyl groups have 2 to 8 carbon atoms and are linear, branched, or alicyclic groups), dialkyl maleate (the two alkyl groups have 2 to 8 carbon atoms and are linear, branched, or alicyclic groups), poly(meth)aryloxyalkane, vinyl monomers having a polyalkylene glycol chain, and poly(meth)acrylates.
[0168] Examples of the alkyl (meth)acrylate having an alkyl group having 1 to 50 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, dodecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, eicosyl (meth)acrylate, and behenyl (meth)acrylate.
[0169] Examples of the poly(meth)allyloxyalkane include diallyloxyethane, triaryloxyethane, tetraaryloxyethane, tetraaryloxypropane, tetraaryloxybutane, and tetrametharyloxyethane.
[0170] Examples of the vinyl monomer having a polyalkylene glycol chain include polyethylene glycol (molecular weight 300) mono(meth)acrylate, polypropylene glycol (molecular weight 500) monoacrylate, methyl alcohol ethylene oxide 10 mol adduct (meth)acrylate, and lauryl alcohol ethylene oxide 30 mol adduct (meth)acrylate.
[0171] Examples of the poly(meth)acrylate include poly(meth)acrylate of polyhydric alcohol, ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and polyethylene glycol di(meth)acrylate.
[0172] The vinyl (thio)ethers include, for example, vinyl methyl ether.
[0173] The vinyl ketone may, for example, be vinyl methyl ketone.
[0174] (10) Other vinyl monomers Examples of the other vinyl monomers include tetrafluoroethylene, fluoroacrylate, isocyanatoethyl (meth)acrylate, and m-isopropenyl-α,α-dimethylbenzyl isocyanate.
[0175] From the viewpoint of low-temperature fixability, the organic fine particles A are preferably a styrene-(meth)acrylic acid ester copolymer and a (meth)acrylic acid ester copolymer, and more preferably a styrene-(meth)acrylic acid ester copolymer.
[0176] From the viewpoint of low-temperature fixability, the resin (a2) is preferably a styrene-(meth)acrylic acid ester copolymer or a (meth)acrylic acid ester copolymer, and more preferably a styrene-(meth)acrylic acid ester copolymer.
[0177] The loss modulus G″ of the viscoelastic properties of the resin (a1) at a frequency of 1 Hz and at 100° C. is preferably 1.5 MPa to 100 MPa, more preferably 1.7 MPa to 30 MPa, and even more preferably 2.0 MPa to 10 MPa. The loss modulus G″ of the viscoelastic properties of the resin (a2) at 100° C. and a frequency of 1 Hz is preferably 0.01 MPa to 1.0 MPa, more preferably 0.02 MPa to 0.5 MPa, and even more preferably 0.05 MPa to 0.3 MPa. When the loss modulus G" of the resin (a1) is 1.5 MPa or more and 100 MPa or less, and the loss modulus G" of the resin (a2) is 0.01 MPa or more and 1.0 MPa or less, the resin fine particles (A) containing the resin (a1) and the resin (a2) as constituents are likely to form a toner present on the surface of the toner base particle, which is preferable.
[0178] The loss modulus G″ of the viscoelastic properties in the present invention is measured, for example, using a viscoelasticity measuring device (ARES-24A (manufactured by Rheometrics)) under the following conditions. Fixture: 25mm parallel plate Frequency: 1Hz Distortion rate: 10% Heating rate: 5℃ / min
[0179] The loss modulus G″ of the viscoelastic properties of the resins (a1) and (a2) at a frequency of 1 Hz and 100° C. can be adjusted by changing the types and composition ratio of the constituent monomers, polymerization conditions (types and amounts of initiator and chain transfer agent, reaction temperature, etc.), etc. Specific examples of the method for adjusting the loss modulus G″ include the following (i) to (iii).
[0180] (i) Adjustment by glass transition temperature (Tg) In the present invention, the glass transition temperature (Tg) calculated from the constituent monomers of the resin (a1) is defined as (Tg1). In the present invention, the glass transition temperature (Tg) calculated from the constituent monomers of the resin (a2) is defined as (Tg2). The glass transition temperature (Tg1) is preferably 0°C or higher and 150°C or lower, and more preferably 50°C or higher and 100°C or lower. It is preferable that the glass transition temperature (Tg1) is 0° C. or higher, since a toner having excellent heat resistance and storage stability can be obtained.It is preferable that the glass transition temperature (Tg1) is 150° C. or lower, since there is little inhibition of heat conduction during fixing of the toner. The glass transition temperature (Tg2) is preferably from -30°C to 100°C, more preferably from 0°C to 80°C, and even more preferably from 30°C to 60°C. When the glass transition temperature (Tg2) is −30° C. or higher, a toner having excellent heat resistance and storage stability can be obtained. When the glass transition temperature (Tg2) is 100° C. or lower, the toner of the present invention is preferably less hindered in heat conduction during fixing.
[0181] The glass transition temperature (Tg1) of the resin (a1) is preferably higher than the glass transition temperature (Tg2) of the resin (a2). Furthermore, the glass transition temperature (Tg1) of the resin (a1) is more preferably 10° C. or more higher, and even more preferably 20° C. or more higher than the glass transition temperature (Tg2) of the resin (a2). By doing so, it becomes easy to form a toner having the fine resin particles (A) on the surface of the toner base particles, and a toner exhibiting excellent low-temperature fixability can be obtained, which is preferable.
[0182] In the present invention, the glass transition temperature (Tg) calculated from the constituent monomers is a value that can be calculated by the Fox method. Here, the Fox method [Tg Fox, Phys. Rev., 86, 652 (1952)] is a method for estimating the Tg of a copolymer from the Tg of each homopolymer, as shown in the following (Equation 4). 1 / Tg=W1 / Tg1+W2 / Tg2+ +Wn / Tgn (Formula 4) In formula 1, Tg represents the glass transition temperature (expressed in absolute temperature) of the copolymer, Tg1, Tg2,...Tgn represent the glass transition temperatures (expressed in absolute temperature) of homopolymers of each monomer component, and W1, W2,...Wn represent the weight fractions of each monomer component.
[0183] In the present invention, Tg can be measured by the method (DSC) specified in ASTM D3418-82 using "DSC20, SSC / 580" (manufactured by Seiko Instruments Inc.).
[0184] (ii) Acid Value (AV) Adjustment In the present invention, the acid value (AV) of the resin (a1) is defined as (AVa1). In the present invention, the acid value (AV) of the resin (a2) is designated as (AVa2). The acid value (AVa1) of the resin (a1) is preferably 75 mgKOH / g or more and 400 mgKOH / g or less, and more preferably 150 mgKOH / g or more and 300 mgKOH / g or less. The acid value (AVa2) of the resin (a2) is preferably 0 mgKOH / g or more and 50 mgKOH / g or less, more preferably 0 mgKOH / g or more and 20 mgKOH / g or less, and even more preferably 0 mgKOH / g, in order to obtain a toner that exhibits excellent low-temperature fixing properties. The acid value (AVa1) of the resin (a1) is from 75 mgKOH / g to 400 mgKOH / g, and the acid value (AVa2) of the resin (a2) is from 0 mgKOH / g to 50 mgKOH / g, which is preferable because it facilitates the formation of a toner having the resin fine particles (A) containing the resin (a1) and the resin (a2) as constituent components on the surface of the toner base particle. The acid value is a theoretical acid value calculated from the molar amount of acidic groups contained in the constituent monomers and the total mass of the constituent monomers. The acid value in the present invention can be measured by the method of JIS K0070:1992.
[0185] When the acid value (AVa1) of the resin (a1) is 75 mgKOH / g or more and 400 mgKOH / g or less, the resin (a1) is preferably a resin containing methacrylic acid and / or acrylic acid. In this case, the content of methacrylic acid and / or acrylic acid in the resin (a1) is preferably 10 mass% or more and 60 mass% or less, more preferably 30 mass% or more and 50 mass% or less, based on the total mass of the resin (a1). When the acid value (AVa2) of the resin (a2) is 0 mgKOH / g or more and 50 mgKOH / g or less, the resin (a2) is preferably a resin containing methacrylic acid and / or acrylic acid. In this case, the content of methacrylic acid and / or acrylic acid in the resin (a2) is preferably 0 mass% or more and 7.5 mass% or less, more preferably 0 mass% or more and 2.5 mass% or less, based on the total mass of the resin (a2).
[0186] It is preferable that the resins (a1) and (a2) satisfy the desired ranges for (i) the glass transition temperature (Tg) and (ii) the acid value (AV), and contain styrene as a constituent monomer. The content of styrene in the resin (a1) is preferably 10% by mass or more and 80% by mass or less, and more preferably 30% by mass or more and 60% by mass or less, based on the total mass of the resin (a1). In this case, the content of methacrylic acid and / or acrylic acid in the resin (a1) is preferably 10% by mass or more and 60% by mass or less, and more preferably 30% by mass or more and 50% by mass or less, based on the total mass of the resin (a1). The content of styrene in the resin (a2) is preferably 10% by mass or more and 100% by mass or less, and more preferably 30% by mass or more and 90% by mass or less, based on the total mass of the resin (a2). In this case, the content of methacrylic acid and / or acrylic acid in the resin (a2) is preferably 0% by mass or more and 7.5% by mass or less, and more preferably 0% by mass or more and 2.5% by mass or less, based on the total mass of the resin (a2).
[0187] The number average molecular weight (Mn) of the resin (a1) is preferably 2,000 or more and 2,000,000 or less, more preferably 20,000 or more and 200,000 or less. If the number average molecular weight (Mn) of the resin (a1) is 2,000 or more, a toner exhibiting excellent heat-resistant storage stability can be obtained. If the number average molecular weight (Mn) of the resin (a1) is 2,000,000 or less, the toner of the present invention is preferably less hindered by heat conduction during fixing. The number average molecular weight (Mn) of the resin (a2) is preferably 1,000 or more and 1,000,000 or less, and more preferably 10,000 or more and 100,000 or less. If the number average molecular weight (Mn) of the resin (a2) is 1,000 or more, a toner exhibiting excellent heat-resistant storage stability can be obtained. If the number average molecular weight (Mn) of the resin (a2) is 1,000,000 or less, it is preferable because the inhibition of heat conduction during fixing of the toner is small.
[0188] The weight average molecular weight (Mw) of the resin (a1) is preferably 20,000 or more and 20,000,000 or less, and more preferably 200,000 or more and 2,000,000 or less. When the weight average molecular weight (Mw) of the resin (a1) is 20,000 or more, a toner exhibiting excellent heat-resistant storage stability can be obtained. When the weight average molecular weight (Mw) of the resin (a1) is 20,000,000 or less, it is preferable because the inhibition of heat conduction during fixing of the toner is small. The weight average molecular weight (Mw) of the resin (a2) is preferably 10,000 or more and 10,000,000 or less, and more preferably 100,000 or more and 1,000,000 or less. When the weight average molecular weight (Mw) of the resin (a2) is 10,000 or more, a toner exhibiting excellent heat-resistant storage stability can be obtained. When the weight average molecular weight (Mw) of the resin (a2) is 10,000,000 or less, it is preferable because the inhibition of heat conduction during fixing of the toner is small.
[0189] The weight average molecular weight (Mw) of the resin (a1) is preferably larger than the weight average molecular weight (Mw) of the resin (a2). Furthermore, the weight average molecular weight (Mw) of the resin (a1) is preferably 1.5 times or more larger than the weight average molecular weight (Mw) of the resin (a2), and more preferably 2.0 times or more larger. By doing so, it becomes easy to form a toner having the resin fine particles (A) containing the resin (a1) and the resin (a2) as constituent components on the surface of the toner base particle, and it is preferable because a toner exhibiting excellent low-temperature fixing property can be obtained.
[0190] Among these, it is preferred that the weight average molecular weight (Mw) of the resin (a1) is 200,000 or more and 2,000,000 or less, the weight average molecular weight (Mw) of the resin (a2) is 100,000 or more and 500,000 or less, and the weight average molecular weight (Mw) of the resin (a1) is larger than the weight average molecular weight (Mw) of the resin (a2).
[0191] The mass ratio of the resin (a1) to the resin (a2) in the resin microparticles (A) (resin (a1) / resin (a2)) is preferably 5 / 95 or more and 95 / 5 or less, more preferably 25 / 75 or more and 75 / 25 or less, and even more preferably 40 / 60 or more and 60 / 40 or less. When the mass ratio (resin (a1) / resin (a2)) is 5 / 95 or more, a toner exhibiting excellent heat-resistant storage stability can be obtained. When the mass ratio (resin (a1) / resin (a2)) is 95 / 5 or less, it is preferable because a toner having the resin fine particles (A) containing the resin (a1) and the resin (a2) as constituents on the surface of the toner base particle can be easily formed.
[0192] The resin (a1) has a solubility parameter (hereinafter sometimes referred to as the SP value) of 9 (cal / cm 3 ) 1 / 2 More than 13(cal / cm 3 ) 1 / 2 It is preferable that the calorie content is 9.5 (cal / cm 3 ) 1 / 2 More than 12.5(cal / cm 3 ) 1 / 2 More preferably, it is 10.5 (cal / cm 3 ) 1 / 2 More than 11.5(cal / cm 3 ) 1 / 2 It is even more preferable that: The SP value of the resin (a2) is 8.5 (cal / cm 3 ) 1 / 2 More than 12.5(cal / cm 3 ) 1 / 2 It is preferable that the cal / cm 3 ) 1 / 2 More than 12(cal / cm 3 ) 1 / 2 More preferably, it is 10 (cal / cm 3 ) 1 / 2 More than 11(cal / cm 3 ) 1 / 2 It is even more preferable that: This is preferable because it makes it easier to form a toner in which the fine resin particles (A) adhere to the surfaces of the toner base particles.
[0193] The SP values of the resin (a1) and the resin (a2) can be adjusted by changing the types and composition ratio of the constituent monomers. The SP value in the present invention can be calculated by the method by Fedors [Polym. Eng. Sci. 14(2)152, (1974)].
[0194] The resin microparticles (A) containing the resin (a1) and the resin (a2) as constituents in the same particle can be produced by known production methods, such as the following production methods (I) to (V). Any of the following production methods (I) to (V) can be suitably used.
[0195] (I) A method of performing seed polymerization of constituent monomers of resin (a2) using fine particles of resin (a1) in an aqueous dispersion as seeds. Specific examples of the method (I) include a method in which the constituent monomers of the resin (a1) are polymerized by dropwise polymerization to produce an aqueous dispersion of resin fine particles containing the resin (a1), and then the aqueous dispersion is used as a seed to perform seed polymerization of the constituent monomers of the resin (a2); and a method in which the resin (a1) produced in advance by solution polymerization or the like is emulsified and dispersed in water, and then the emulsion is used as a seed to perform seed polymerization of the constituent monomers of the resin (a2).
[0196] (II) A method of performing seed polymerization of constituent monomers of resin (a1) using fine particles of resin (a2) in an aqueous dispersion as seeds. Specific examples of the method (II) include a method in which the constituent monomers of the resin (a2) are polymerized by dropwise polymerization to produce an aqueous dispersion of resin fine particles containing the resin (a2), and then the aqueous dispersion is used as a seed to perform seed polymerization of the constituent monomers of the resin (a1); and a method in which the resin (a2) produced in advance by solution polymerization or the like is emulsified and dispersed in water, and then the emulsion is used as a seed to perform seed polymerization of the constituent monomers of the resin (a1).
[0197] (III) A method in which a mixture of resin (a1) and resin (a2) is emulsified in an aqueous medium to obtain an aqueous dispersion of resin fine particles. A specific example of the method (III) is a method in which a solution or melt of the resin (a1) and the resin (a2) which have been produced in advance by solution polymerization or the like is mixed, and then the mixture is emulsified and dispersed in an aqueous medium.
[0198] (IV) A method in which a mixture of the resin (a1) and the constituent monomers of the resin (a2) is emulsified in an aqueous medium, and then the constituent monomers of the resin (a2) are polymerized to obtain an aqueous dispersion of resin fine particles. Specific examples of the above-mentioned (IV) include a method in which the resin (a1) previously produced by solution polymerization or the like is mixed with the constituent monomers of the resin (a2), the mixture is emulsified and dispersed in an aqueous medium, and then the constituent monomers of the resin (a2) are polymerized; and a method in which the resin (a1) is produced in the constituent monomers of the resin (a2), the mixture is emulsified and dispersed in an aqueous medium, and then the constituent monomers of the resin (a2) are polymerized.
[0199] (V) A method in which a mixture of resin (a2) and monomers constituting resin (a1) is emulsified in an aqueous medium, and then the monomers constituting resin (a1) are polymerized to obtain an aqueous dispersion of resin fine particles. Specific examples of the (V) include a method in which the resin (a2) previously produced by solution polymerization or the like is mixed with the constituent monomers of the resin (a1), the mixture is emulsified and dispersed in an aqueous medium, and then the constituent monomers of the resin (a1) are polymerized; and a method in which the resin (a2) is produced in the constituent monomers of the resin (a1), the mixture is emulsified and dispersed in an aqueous medium, and then the constituent monomers of the resin (a1) are polymerized.
[0200] In addition, the resin microparticles obtained by the methods (I) to (V) may be resin microparticles (A) containing resin (a1) and resin (a2) as constituent components within the same particle, as well as mixtures containing resin microparticles whose only constituent resin component is resin (a1) and resin microparticles whose only constituent resin component is resin (a2). In the composite process described below, the mixture may be used as is, or only the resin microparticles (A) may be isolated and used.
[0201] The fact that the organic microparticles (A) contain the resin (a1) and the resin (a2) as constituent components within the same particle can be confirmed by observing element mapping images of a cut surface of the resin microparticles (A) using a known surface elemental analysis device (TOF-SIMS, EDX-SEM, etc.), and by observing electron microscope images of a cut surface of the resin microparticles (A) stained with a stain corresponding to the functional groups contained in the resin (a1) and the resin (a2).
[0202] The resin fine particles (A) are preferably used in the form of an aqueous dispersion. The aqueous medium in the aqueous dispersion is not particularly limited as long as it is a liquid containing water as an essential component, and examples thereof include an aqueous solution containing a surfactant A. Furthermore, the aqueous dispersion may contain a buffer material, a protective colloid, and the like, as necessary.
[0203] -Other Ingredients B- Examples of the other component B include other resin components, initiators (and their residues), chain transfer agents, antioxidants, plasticizers, preservatives, reducing agents, and organic solvents.
[0204] --Other resin components-- The other resin components are not particularly limited and can be appropriately selected depending on the purpose. Examples of the other resin components include vinyl resins other than the resins used in the resin (a1) and the resin (a2), polyurethane resins, epoxy resins, polyester resins, polyamide resins, polyimide resins, silicon resins, phenol resins, melamine resins, urea resins, aniline resins, ionomer resins, polycarbonate resins, and the like. These may be used alone or in combination of two or more.
[0205] --Initiator (and its residues)-- The initiator (and its residue) is not particularly limited, and examples thereof include known radical polymerization initiators. Specific examples of the initiator and its residue include persulfate initiators such as potassium persulfate and ammonium persulfate, azo initiators such as azobisisobutyronitrile, organic peroxides such as benzoyl peroxide, cumene hydroperoxide, tert-butyl hydroperoxide, tert-butyl peroxyisopropyl monocarbonate, and tert-butyl peroxybenzoate, and hydrogen peroxide. These may be used alone or in combination of two or more.
[0206] --Chain transfer agent-- The chain transfer agent is not particularly limited and can be appropriately selected depending on the purpose. Examples of the chain transfer agent include n-dodecyl mercaptan, tert-dodecyl mercaptan, n-butyl mercaptan, 2-ethylhexyl thioglycolate, 2-mercaptoethanol, β-mercaptopropionic acid, and α-methylstyrene dimer. These may be used alone or in combination of two or more.
[0207] --Chain transfer agent-- The antioxidant is not particularly limited and can be appropriately selected depending on the purpose. Examples of the antioxidant include phenol compounds, paraphenylenediamine, hydroquinone, organic sulfur compounds, and organic phosphorus compounds. Examples of the phenol compound include 2,6-di-t-butyl-p-cresol, butylated hydroxyanisole, 2,6-di-t-butyl-4-ethylphenol, stearyl-β-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, 2,2′-methylene-bis-(4-methyl-6-t-butylphenol), 2,2′-methylene-bis-(4-ethyl-6-t-butylphenol), 4,4′-thiobis-(3-methyl-6-t-butylphenol), 4,4′-butylidenebis-(3-methyl-6-t-butylphenol), and 4,4′-butylidenebis-(3-methyl-6-t-butylphenol). methyl-6-t-butylphenol), 1,1,3-tris-(2-methyl-4-hydroxy-5-t-butylphenyl)butane, 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane, bis[3,3'-bis(4'-hydroxy-3'-t-butylphenyl)butyric acid]glycol ester, tocopherol, etc. Examples of the paraphenylenediamine include N-phenyl-N'-isopropyl-p-phenylenediamine, N,N'-di-sec-butyl-p-phenylenediamine, N-phenyl-N-sec-butyl-p-phenylenediamine, N,N'-di-isopropyl-p-phenylenediamine, and N,N'-dimethyl-N,N'-di-t-butyl-p-phenylenediamine. Examples of the hydroquinone include 2,5-di-t-octylhydroquinone, 2,6-didodecylhydroquinone, 2-dodecylhydroquinone, 2-dodecyl-5-chlorohydroquinone, 2-t-octyl-5-methylhydroquinone, and 2-(2-octadecenyl)-5-methylhydroquinone. Examples of the organic sulfur compound include dilauryl-3,3'-thiodipropionate, distearyl-3,3'-thiodipropionate, and ditetradecyl-3,3'-thiodipropionate. Examples of the organic phosphorus compound include triphenylphosphine, tri(nonylphenyl)phosphine, tri(dinonylphenyl)phosphine, tricresylphosphine, and tri(2,4-dibutylphenoxy)phosphine. These may be used alone or in combination of two or more.
[0208] --Plasticizer-- The plasticizer is not particularly limited and can be appropriately selected depending on the purpose. Examples of the plasticizer include phthalate esters, aliphatic dibasic acid esters, trimellitate esters, phosphate esters, and fatty acid esters. Examples of the phthalate ester include dibutyl phthalate, dioctyl phthalate, butyl benzyl phthalate, and diisodecyl phthalate. Examples of the aliphatic dibasic acid ester include di-2-ethylhexyl adipate and 2-ethylhexyl sebacate. Examples of the trimellitic acid ester include tri-2-ethylhexyl trimellitate and trioctyl trimellitate. Examples of the phosphate ester include triethyl phosphate, tri-2-ethylhexyl phosphate, and tricresyl phosphate. The fatty acid ester may, for example, be butyl oleate. These may be used alone or in combination of two or more.
[0209] --Preservatives-- The preservative is not particularly limited and can be appropriately selected depending on the purpose. Examples of the preservative include organic nitrogen sulfur compound preservatives and organic sulfur halide preservatives.
[0210] --Reducing agent-- The reducing agent is not particularly limited and can be appropriately selected depending on the purpose. Examples of the reducing agent include reducing organic compounds such as ascorbic acid, tartaric acid, citric acid, glucose, and formaldehyde sulfoxylate metal salts; and reducing inorganic compounds such as sodium thiosulfate, sodium sulfite, sodium bisulfite, and sodium metabisulfite.
[0211] --Organic solvents-- The organic solvent is not particularly limited and can be appropriately selected depending on the purpose. Examples of the organic solvent include ketone solvents such as acetone and methyl ethyl ketone (MEK); ester solvents such as ethyl acetate and γ-butyrolactone; ether solvents such as THF; amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone and N-methylcaprolactam; alcohol solvents such as isopropyl alcohol; and aromatic hydrocarbon solvents such as toluene and xylene. These may be used alone or in combination of two or more.
[0212] <Resin fine particles (B)> The resin fine particles (B) are preferably composed of one type of styrene-acrylic resin. The resin fine particles (B) can be obtained by the same production method as that for the resin (a1). The resin fine particles (B) are preferably used in the form of an aqueous dispersion, similarly to the resin fine particles (A). The aqueous medium in the aqueous dispersion is not particularly limited as long as it is a liquid containing water as an essential component, and examples thereof include an aqueous solution containing a surfactant A. Furthermore, the aqueous dispersion may contain a buffer material, a protective colloid, and the like, as necessary.
[0213] The surfactant A in the aqueous dispersion of the resin fine particles (A) and the resin fine particles (B) is not particularly limited and can be appropriately selected depending on the purpose. Examples of the surfactant A include nonionic surfactants, anionic surfactants, cationic surfactants, amphoteric surfactants, and other surfactants.
[0214] -Nonionic surfactants- The nonionic surfactant is not particularly limited and can be appropriately selected depending on the purpose. Examples of the nonionic surfactant include AO addition type nonionic surfactants and polyhydric alcohol type nonionic surfactants.
[0215] --AO-added nonionic surfactants-- Examples of the AO-addition type nonionic surfactant include an EO adduct of an aliphatic alcohol having from 10 to 20 carbon atoms, an EO adduct of a phenol, an EO adduct of a nonylphenol, an EO adduct of an alkylamine having from 8 to 22 carbon atoms, and an EO adduct of poly(oxypropylene) glycol.
[0216] --Polyhydric alcohol type nonionic surfactants-- Examples of the polyhydric alcohol type nonionic surfactant include fatty acid (carbon number 8 to 24) esters of polyhydric (trivalent to octavalent, or octavalent or more) alcohols (carbon number 2 to 30), alkyl (carbon number 4 to 24) poly(degree of polymerization 1 to 10) glycosides, and the like. These may be used alone or in combination of two or more. Examples of the fatty acid (having 8 to 24 carbon atoms) esters of polyhydric (having 3 to 8 valences, or 8 or more valences) alcohols (having 2 to 30 carbon atoms) include glycerin monostearate, glycerin monooleate, sorbitan monolaurate, and sorbitan monooleate. These may be used alone or in combination of two or more.
[0217] -Anionic surfactants- Examples of the anionic surfactant include ether carboxylic acids or salts thereof having a hydrocarbon group having from 8 to 24 carbon atoms, sulfate esters or ether sulfate esters and salts thereof having a hydrocarbon group having from 8 to 24 carbon atoms, sulfonates having a hydrocarbon group having from 8 to 24 carbon atoms, sulfosuccinates having one or two hydrocarbon groups having from 8 to 24 carbon atoms, phosphate esters or ether phosphate esters and salts thereof having a hydrocarbon group having from 8 to 24 carbon atoms, fatty acid salts having a hydrocarbon group having from 8 to 24 carbon atoms, and acylated amino acid salts having a hydrocarbon group having from 8 to 24 carbon atoms.
[0218] --Ether carboxylic acid or its salt having a hydrocarbon group having 8 to 24 carbon atoms-- Examples of the ether carboxylic acid or salt thereof having a hydrocarbon group having 8 to 24 carbon atoms include sodium lauryl ether acetate and (poly)oxyethylene (molar number of addition: 1 to 100) sodium lauryl ether acetate. These may be used alone or in combination of two or more.
[0219] --Sulfuric acid esters or ether sulfates having a hydrocarbon group having from 8 to 24 carbon atoms and their salts-- Examples of the sulfate ester or ether sulfate ester having a hydrocarbon group having 8 to 24 carbon atoms and salts thereof include sodium lauryl sulfate, (poly)oxyethylene (number of moles added: 1 to 100) sodium lauryl sulfate, (poly)oxyethylene (number of moles added: 1 to 100) triethanolamine lauryl sulfate, (poly)oxyethylene (number of moles added: 1 to 100) sodium coconut oil fatty acid monoethanolamide sulfate, and the like. These may be used alone or in combination of two or more.
[0220] --Sulfonate having a hydrocarbon group having 8 to 24 carbon atoms-- Examples of the sulfonate salt having a hydrocarbon group having 8 to 24 carbon atoms include sodium dodecylbenzenesulfonate. These may be used alone or in combination of two or more.
[0221] --Phosphate esters or ether phosphate esters having a hydrocarbon group having 8 to 24 carbon atoms and their salts-- Examples of the phosphate ester or ether phosphate ester having a hydrocarbon group having 8 to 24 carbon atoms and salts thereof include sodium lauryl phosphate and sodium (poly)oxyethylene (addition mole number 1 to 100) lauryl ether phosphate. These may be used alone or in combination of two or more.
[0222] --Salt of fatty acid having a hydrocarbon group having 8 to 24 carbon atoms-- Examples of the fatty acid salt having a hydrocarbon group having 8 to 24 carbon atoms include sodium laurate and triethanolamine laurate. These may be used alone or in combination of two or more.
[0223] --Acylated amino acid salt having a hydrocarbon group having 8 to 24 carbon atoms-- Examples of the acylated amino acid salts having a hydrocarbon group having 8 to 24 carbon atoms include sodium methyl coconut taurate, sodium coconut sarcosine, triethanolamine coconut sarcosine, N-triethanolamine coconut acyl-L-glutamate, sodium N-sodium coconut acyl-L-glutamate, and sodium lauroylmethyl-β-alanine. These may be used alone or in combination of two or more.
[0224] -Cationic surfactants- Examples of the cationic surfactant include quaternary ammonium salt types and amine salt types.
[0225] --Quaternary ammonium salt type-- Examples of the quaternary ammonium salt type include stearyl trimethyl ammonium chloride, behenyl trimethyl ammonium chloride, distearyl dimethyl ammonium chloride, lanolin fatty acid aminopropyl ethyl dimethyl ammonium ethyl sulfate, and the like. These may be used alone or in combination of two or more.
[0226] --Amine salt type-- Examples of the amine salt type include stearic acid diethylaminoethylamide lactate, dilaurylamine hydrochloride, and oleylamine lactate. These may be used alone or in combination of two or more.
[0227] -Amphoteric surfactant- Examples of the amphoteric surfactant include betaine-type amphoteric surfactants and amino acid-type amphoteric surfactants.
[0228] --Betaine-type amphoteric surfactant-- Examples of the betaine type amphoteric surfactant include coconut oil fatty acid amidopropyl dimethylaminoacetic acid betaine, lauryl dimethylaminoacetic acid betaine, 2-alkyl-N-carboxymethyl-N-hydroxyethyl imidazolinium betaine, and lauryl hydroxysulfobetaine. These may be used alone or in combination of two or more.
[0229] --Amino acid type amphoteric surfactant-- Examples of the amino acid type amphoteric surfactant include sodium β-laurylaminopropionate. These may be used alone or in combination of two or more.
[0230] -Other surfactants- Examples of the other surfactants include reactive surfactants and emulsifying dispersants. The reactive activator is not particularly limited as long as it has radical reactivity, and can be appropriately selected depending on the purpose. The reactive activator may be a synthesized product or a commercially available product. Specific examples of commercially available reactive activators include ADEKA REASOAP (registered trademark) SE-10N, SR-10, SR-20, SR-30, ER-20, and ER-30 (all manufactured by ADEKA Corporation); AQUALON (registered trademark) HS-10, KH-05, KH-10, and KH-1025 (all manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.); ELEMINOL (registered trademark) JS-20 (manufactured by Sanyo Chemical Industries, Ltd.); LATEMUL (registered trademark) PD-104, PD-420, and PD-430 (manufactured by Kao Corporation); and IONET (registered trademark) MO-200 (manufactured by Sanyo Chemical Industries, Ltd.).
[0231] As the surfactant, the nonionic surfactant, the anionic surfactant, or the other surfactant is preferable, in that a toner having a desired shape and a sharp particle size distribution can be obtained by stabilizing the oil droplets during emulsification and dispersion, and it is more preferable to use the nonionic surfactant, the anionic surfactant, and the other surfactant in combination, and it is even more preferable to use the nonionic surfactant or the anionic surfactant in combination with the other surfactant.
[0232] The buffer material in the aqueous dispersion of the resin fine particles (A) and the resin fine particles (B) is not particularly limited and can be appropriately selected depending on the purpose. Examples of the buffer material include sodium acetate, sodium citrate, and sodium bicarbonate. These may be used alone or in combination of two or more. The protective colloid in the aqueous dispersion of the resin fine particles (A) and the resin fine particles (B) is not particularly limited and can be appropriately selected depending on the purpose. Examples of the protective colloid include water-soluble cellulose compounds and alkali metal salts of polymethacrylic acid. These may be used alone or in combination of two or more.
[0233] The resin particles consisting of the resin fine particles (A) and the resin fine particles (B) preferably have an average particle size of 10 nm or more and 40 nm or less, from the viewpoint of maintaining good cleaning properties without impairing low-temperature fixability.
[0234] <Standard deviation of distance between resin particles> In the present invention, the distance between the resin particles refers to the shortest distance between the surface of a resin particle present on the surface of a toner base particle and the surface of an adjacent resin particle that is not in contact with the resin particle. In the present invention, the "shortest distance between the surface of a resin particle present on the surface of a toner base particle and the surface of an adjacent resin particle that is not in contact with the resin particle" is sometimes referred to as the "distance between resin particles."
[0235] In the toner of the present invention, the standard deviation of the shortest distance between the surface of a resin particle present on the surface of a toner base particle and the surface of an adjacent resin particle not in contact with the resin particle is less than 600 nm.Furthermore, it is preferable that the standard deviation of the distance between the resin particles is 300 nm or less. By doing so, the resin particles can be arranged uniformly with gaps on the surface of the toner base material, preventing exposure of materials such as crystalline polyester resin without impeding heat conduction to the toner during fixing, and improving heat-resistant storage stability. In addition, the adhesion strength of inorganic fine particles such as silica and titanium can be adjusted appropriately when they are externally added to the surface of the toner matrix. It has been found that by controlling the amount of the inorganic fine particles liberated from the toner matrix to a certain amount, an appropriate amount of the inorganic fine particles is deposited on the contact surface between the cleaning blade and the photoreceptor, and good cleaning properties can be obtained. Furthermore, since the amount of liberated inorganic fine particles can be controlled to an appropriate amount, the occurrence of abnormal images due to filming can be suppressed.
[0236] There are no particular limitations on the method for making the standard deviation of the distance between adjacent resin particles that are not in contact with each other and are present on the toner surface less than 600 nm. For example, a method of producing a toner using resin particles that combine resin fine particles (A) made of two types of styrene acrylic resins (a1) and (a2) and resin fine particles (B) made of one type of styrene acrylic resin is preferred. In this manner, the resin particles consisting of the resin fine particles (A) and the resin fine particles (B) that have been mixed in advance during emulsification can be uniformly present on the surface of the toner base particles. By removing all or a part of the resin (a1) in the resin fine particles (A) that have adhered to the surface of the toner base particles and the resin fine particles (B) through a washing step described later, the resin fine particles (A) can be uniformly adhered to the surface of the toner base particles with gaps therebetween.
[0237] The method for measuring the distance between the resin particles is not particularly limited and can be appropriately selected depending on the purpose. For example, the distance can be measured from an image observed with a scanning electron microscope (SEM).
[0238] When the distance between the resin particles is measured using a scanning electron microscope (SEM), the distance can be measured, for example, by the following method. 50 ml of a 5% aqueous solution containing a surfactant (product name: Noigen ET-165, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) is added to a 100 ml screw tube, and 3 g of the toner of the present invention is added to the mixture and gently moved up and down and left and right. Then, the mixture is stirred for 30 minutes in a ball mill so that the toner is mixed with the dispersion solution. Next, in order to liberate the external additives, ultrasonic energy is applied under the following conditions using an ultrasonic homogenizer (product name: homogenizer, model VCX750, CV33, manufactured by SONICS & MATERIALS Co., Ltd.). -Ultrasonic conditions- Vibration time: 60 minutes continuous Output: 40W ·Amplitude 40W ·Vibration start temperature 23℃±1.5℃ ·Temperature during vibration 23℃±1.5℃ The dispersion to which ultrasonic energy has been applied is suction filtered using filter paper (product name: Qualitative Filter Paper (No. 2, 110 mm), manufactured by Advantec Toyo Co., Ltd.), washed twice with ion-exchanged water, and then filtered again to remove the liberated additives, after which the toner particles are dried. The toner particles obtained after drying are observed with a scanning electron microscope (SEM). First, the external additives and charge control agent containing Si are detected by observing the reflected electron image, and the reflected electron image is photographed. The reflected electron image obtained is binarized (threshold: 135) using the image processing software "Image-J" to create an image in which the external additives and charge control agent have been removed. Next, a secondary electron image is observed at the same position as the reflected electron image, and the secondary electron image is photographed. The resin fine particles in the present invention are not observed in the reflected electron image, but only in the secondary electron image. The reflected electron image, from which the external additives and the charge control agent have been removed, is compared with the secondary electron image to determine that the particles present in the areas other than the remaining external additives and the remaining charge control agent are resin particles. The distance between the resin particles is measured using the image processing software "Image-J." The scanning electron microscope image can be taken under the following conditions, for example. --Filming conditions-- Scanning electron microscope SU-8230 Magnification: 35,000x Image capture: SE (L) secondary electrons, BSE (backscattered electrons) Acceleration voltage: 2.0 kV ·Acceleration current 1.0μA ·Probe current Normal Focus Mode UHR Working distance 8.0mm The standard deviation of the distance between the resin particles can be calculated from the following formula, where the interparticle distance is x.
[0239]
number
[0240] <Differential Scanning Calorimetry (DSC) of Toner> The glass transition temperature (Tg1st) of the toner of the present invention at the first temperature rise in differential scanning calorimetry (DSC) is preferably 40° C. or higher and 65° C. or lower. The glass transition temperature (Tg1st) at the first temperature rise in DSC of the component of the toner that is insoluble in tetrahydrofuran (THF) is preferably −45° C. or more and 5° C. or less. The glass transition temperature (Tg2nd) of the THF-soluble component of the toner at the second temperature rise in DSC is preferably 20° C. or more and 65° C. or less. The glass transition temperature (Tg1st) in the first temperature rise and the glass transition temperature (Tg2nd) in the second temperature rise in differential scanning calorimetry (DSC) of the toner preferably satisfy Tg1st-Tg2nd≧10° C., from the viewpoint of improving low-temperature fixability and heat-resistant storage stability.
[0241] Here, the glass transition temperature of the toner can be measured, for example, by using a differential scanning calorimeter (DSC-60, manufactured by Shimadzu Corporation). For example, a DSC curve is measured using the above-mentioned differential scanning calorimeter. From the obtained DSC curves, a DSC curve at the first heating is selected using an analysis program, and the glass transition temperature Tg1st at the first heating is obtained using the endothermic shoulder temperature in the analysis program. A DSC curve at the second heating is selected, and the glass transition temperature Tg2nd at the second heating is obtained using the endothermic shoulder temperature.
[0242] <Average particle size of toner> The volume average particle diameter of the toner of the present invention is not particularly limited and can be appropriately selected depending on the purpose, but is preferably from 3.0 to 7.0 μm, more preferably from 4.0 to 6.0 μm, and even more preferably from 5.0 to 6.0 μm. The toner having a volume average particle diameter of 3.0 μm or more can solve the problem of toner dust occurring during primary transfer and secondary transfer, while the toner having a volume average particle diameter of 7.0 μm or less can solve the problem of insufficient dot reproducibility and deterioration of granularity in halftone parts, making it difficult to obtain high-definition images.
[0243] <Toner manufacturing method> The toner production method of the present invention is a method for producing the above-mentioned toner. The method for producing the toner is not particularly limited and may be appropriately selected depending on the purpose. However, it is preferable to granulate the toner by dispersing an oil phase containing the amorphous polyester resin and the modified polyester resin, and further containing the crystalline polyester resin, the release agent, the colorant, etc., in an aqueous medium. It is more preferable that the oil phase containing the amorphous polyester resin and the modified polyester resin, and further containing the crystalline polyester resin, the curing agent, the release agent, the colorant, etc., as necessary, is dispersed in an aqueous medium to perform granulation.
[0244] The toner can be produced by, for example, a known dissolution suspension method. As an example of the known dissolution suspension method, a method of forming toner base particles while generating a polyester resin by an elongation reaction and / or a crosslinking reaction between the prepolymer and the curing agent will be described. In the dissolution suspension method, an aqueous medium is prepared, an oil phase containing toner materials is prepared, the toner materials are emulsified or dispersed, and the organic solvent is removed.
[0245] - Adjustment of aqueous medium (aqueous phase) - The aqueous medium can be prepared, for example, by dispersing resin particles in the aqueous medium. The amount of the resin particles added to the aqueous medium is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.5 parts by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the aqueous medium. The aqueous medium is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include water, a solvent miscible with water, and a mixture thereof. Among these, water is preferred. These may be used alone or in combination of two or more.
[0246] The water-miscible solvent is not particularly limited and can be appropriately selected depending on the purpose. Examples of the water-miscible solvent include alcohol, dimethylformamide, tetrahydrofuran, cellosolves, and lower ketones. Examples of the alcohol include methanol, isopropanol, and ethylene glycol. Examples of the lower ketones include acetone and methyl ethyl ketone.
[0247] - Preparation of oil phase - The oil phase containing the toner materials of the present invention can be prepared by dissolving or dispersing toner materials including two types of amorphous polyester resins, which are prepolymers having at least one of a urethane bond and a urea bond, and a crystalline polyester resin having no urethane bond and / or a urea bond, and further including the crystalline polyester resin, the curing agent, the releasing agent, the colorant, etc., as necessary, in an organic solvent.
[0248] The organic solvent is not particularly limited and can be appropriately selected depending on the purpose, but an organic solvent having a boiling point of less than 150° C. is preferred in terms of ease of removal. Examples of the organic solvent having a boiling point of less than 150° C. include toluene, xylene, benzene, carbon tetrachloride, methylene chloride, 1,2-dichloroethane, 1,1,2-trichloroethane, trichloroethylene, chloroform, monochlorobenzene, dichloroethylidene, methyl acetate, ethyl acetate, methyl ethyl ketone, methyl isobutyl ketone, etc. Among these, ethyl acetate, toluene, xylene, benzene, methylene chloride, 1,2-dichloroethane, chloroform, carbon tetrachloride, etc. are preferred, and ethyl acetate is more preferred. These may be used alone or in combination of two or more.
[0249] -Emulsification or dispersion- The toner materials can be emulsified or dispersed by dispersing an oil phase containing the toner materials in the aqueous medium. When the toner materials are emulsified or dispersed, the curing agent and the prepolymer can be subjected to an elongation reaction and / or a crosslinking reaction. The reaction conditions (reaction time, reaction temperature) for producing the prepolymer are not particularly limited, and can be appropriately selected depending on the combination of the curing agent and the prepolymer. The reaction time is preferably from 10 minutes to 40 hours, and more preferably from 2 hours to 24 hours. The reaction temperature is preferably from 0° C. to 150° C., and more preferably from 40° C. to 98° C.
[0250] The method for stably forming a dispersion liquid containing the prepolymer in the aqueous medium is not particularly limited and may be appropriately selected depending on the purpose. For example, there may be mentioned a method in which an oil phase prepared by dissolving or dispersing a toner material in a solvent is added to an aqueous medium phase, and the oil phase is dispersed by shear force.
[0251] The dispersing machine used for the dispersion is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include a low-speed shearing dispersing machine, a high-speed shearing dispersing machine, a friction dispersing machine, a high-pressure jet dispersing machine, an ultrasonic dispersing machine, etc. Among these, a high-speed shearing dispersing machine is preferred because it can control the particle size of the dispersion (oil droplets) to 2 μm or more and 20 μm or less.
[0252] When the high-speed shear type dispersing machine is used, the conditions such as the rotation speed, dispersing time, and dispersing temperature are not particularly limited and can be appropriately selected depending on the purpose. The rotation speed is preferably 1,000 rpm or more and 30,000 rpm or less, and more preferably 5,000 rpm or more and 20,000 rpm or less. In the case of a batch method, the dispersion time is preferably 0.1 minutes or more and 5 minutes or less. The dispersion temperature under pressure is preferably from 0° C. to 150° C., and more preferably from 40° C. to 98° C. In general, the higher the dispersion temperature, the easier the dispersion.
[0253] The amount of the aqueous medium used when emulsifying or dispersing the toner materials is not particularly limited and can be appropriately selected depending on the purpose. However, the amount is preferably 50 parts by mass or more and 2,000 parts by mass or less, and more preferably 100 parts by mass or more and 1,000 parts by mass or less, relative to 100 parts by mass of the toner materials. If the amount of the aqueous medium used when emulsifying or dispersing the toner materials is less than 50 parts by mass, the dispersion state of the toner materials may be poor, and toner base particles having a predetermined particle size may not be obtained. If the amount of the aqueous medium used when emulsifying or dispersing the toner materials exceeds 2,000 parts by mass, the production cost may increase.
[0254] When emulsifying or dispersing the oil phase containing the toner materials, it is preferable to use a dispersant, since this stabilizes the dispersion such as oil droplets, thereby enabling the toner to have a desired shape and a toner having a sharp particle size distribution. The dispersant is not particularly limited and may be appropriately selected depending on the purpose, and examples thereof include surfactant B, poorly water-soluble inorganic compound dispersants, polymer-based protective colloids, etc. Among these, surfactants are preferred. These may be used alone or in combination of two or more.
[0255] The surfactant B is not particularly limited and can be appropriately selected depending on the purpose. Examples of the surfactant B include nonionic surfactants, anionic surfactants, cationic surfactants, amphoteric surfactants, and other surfactants. Examples of the anionic surfactant include alkylbenzene sulfonate, α-olefin sulfonate, phosphate, etc. Among these, those having a fluoroalkyl group are preferred.
[0256] -Removal of organic solvents- The method for removing the organic solvent from the dispersion is not particularly limited and can be appropriately selected depending on the purpose. Examples of the method include a method in which the temperature of the entire reaction system is gradually increased to evaporate the organic solvent in the oil droplets, and a method in which the dispersion is sprayed into a dry atmosphere to remove the organic solvent in the oil droplets. When the organic solvent is removed, toner base particles are formed, which may then be subjected to a washing process, a drying process, a classification process, and the like. The classification step may be carried out by removing fine particles in a liquid using a cyclone, a decanter, centrifugal separation, or the like, or the classification step may be carried out after drying.
[0257] In the washing step, examples of a method for removing all or a part of the resin (a1) in the resin fine particles (A) present on the surface of the toner base particles and the resin fine particles (B) include chemical methods. Among the cleaning steps using the chemical methods, a method in which an alkaline aqueous solution is added to and mixed with the toner base particles to dissolve all or a part of the resin (a1) in the resin fine particles (A) present on the surface of the toner base particles and the resin fine particles (B) is preferred.
[0258] The alkali in the alkaline aqueous solution is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include hydroxides of alkali metals such as potassium hydroxide and sodium hydroxide, ammonia, etc. Among these, potassium hydroxide and sodium hydroxide are preferred because they can easily dissolve the resin (a1) and the resin fine particles (B). The pH of the alkali contained in the alkaline aqueous solution is preferably 8 or more and 14 or less, and more preferably 10 or more and 12 or less.
[0259] In the washing step, the toner base particles and the alkaline aqueous solution can be mixed, for example, by dropping the alkaline aqueous solution into a slurry of the toner base particles under stirring. If necessary, an acid aqueous solution may be dropped to neutralize the mixture.
[0260] The toner base particles obtained by the toner manufacturing method may be mixed with particles of the external additive, the charge control agent, etc. In this case, by applying a mechanical impact force, it is possible to suppress the particles of the external additive, etc. from being detached from the surface of the toner base particles. The method of applying the mechanical impact force is not particularly limited and can be appropriately selected depending on the purpose. Examples of the method include a method of applying an impact force to the mixture using a blade rotating at high speed, and a method of introducing the mixture into a high-speed air stream and accelerating it to cause particles to collide with each other or with an appropriate collision plate.
[0261] The device used in the method of applying the mechanical impact force is not particularly limited and can be appropriately selected depending on the purpose. Examples of the device include an Angmill (manufactured by Hosokawa Micron Corporation), a device obtained by modifying an I-type mill (manufactured by Japan Pneumatic Co., Ltd.) to reduce the grinding air pressure, a Hybridization System (manufactured by Nara Machinery Works), a Cryptron System (manufactured by Kawasaki Heavy Industries, Ltd.), and an automatic mortar.
[0262] (Developer) The developer of the present invention contains at least the toner of the present invention, and contains other components as necessary. Since the maximum diameter of the domain of the crystalline polyester resin in the toner of the present invention is 1.5 μm or less, the state of dispersion inside the toner becomes uniform, so that high-quality images can be stably formed, and the developer is also excellent in transferability and chargeability. The developer may be a one-component developer or a two-component developer, but when used in a high-speed printer that corresponds to the recent improvement in information processing speed, a two-component developer is preferred because it has an improved life. When the developer is used as a one-component developer, even if the toner is balanced, there is little variation in the particle size of the toner, there is little filming of the toner on the developing roller, and there is little melting of the toner to components such as blades that thin the toner layer, and good and stable developability and images can be obtained even with long-term stirring in the developing device.
[0263] <Career> The carrier in the developer is not particularly limited and can be appropriately selected depending on the purpose, but is preferably one having a core material and a resin layer covering the core material.
[0264] -Core material- The material of the core material is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include manganese-strontium-based materials having an average particle size of 50 emu / g or more and 90 emu / g or less, manganese-magnesium-based materials having an average particle size of 50 emu / g or more and 90 emu / g or less, etc. In order to ensure image density, it is preferable to use highly magnetized materials such as iron powder having an average particle size of 100 emu / g or more, magnetite having an average particle size of 75 emu / g or more and 120 emu / g or less, etc. In addition, it is preferable to use a low magnetization material such as a copper-zinc material having a magnetization rate of 30 emu / g or more and 80 emu / g or less, since this can reduce the impact of the developer in a standing state on the photoconductor and is advantageous for improving image quality. These may be used alone or in combination of two or more.
[0265] The volume average particle diameter of the core material is not particularly limited and can be appropriately selected depending on the purpose, but is preferably from 10 μm to 150 μm, and more preferably from 40 μm to 100 μm. If the volume average particle diameter of the core material is less than 10 μm, the amount of fine powder in the carrier increases, the magnetization per particle decreases, and the carrier may scatter. If the volume average particle diameter of the core material exceeds 150 μm, the specific surface area decreases, which may cause toner scattering, and in the case of full color toner with many solid areas, reproduction of the solid areas may be particularly poor.
[0266] The toner of the present invention can be mixed with the carrier and used in a two-component developer. The content of the carrier in the two-component developer is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 90 parts by mass or more and 98 parts by mass or less, and more preferably 93 parts by mass or more and 97 parts by mass or less, relative to 100 parts by mass of the two-component developer. The developer of the present invention can be suitably used for image formation by various known electrophotographic methods such as a magnetic one-component development method, a non-magnetic one-component development method, and a two-component development method.
[0267] -Resin layer- The resin layer is not particularly limited and can be appropriately selected depending on the purpose. For example, a silicone resin can be used.
[0268] (Toner storage container) The toner storage container for storing the toner of the present invention is easy to store, transport, and the like, and has excellent handleability, and therefore can be detachably attached to a process cartridge, an image forming apparatus, etc., which will be described later, and used for replenishing a developer. The toner stored in the toner storage container may be in the form of a developer. The toner storage container is not particularly limited and can be appropriately selected from known containers. For example, the toner storage container can include a container body and a cap.
[0269] The shape of the toner storage container is not particularly limited and may be appropriately selected depending on the purpose, but is preferably cylindrical. Furthermore, it is preferable that the inner peripheral surface is formed with a spiral unevenness so that the toner or developer contained therein can be transferred to the outlet side by rotating the container, and that a part or all of the spiral unevenness has a bellows function. The material of the toner storage container is not particularly limited and can be appropriately selected depending on the purpose. From the viewpoint of good dimensional accuracy, however, resins such as polyester resin, polyethylene resin, polypropylene resin, polystyrene resin, polyvinyl chloride resin, polyacrylic acid, polycarbonate resin component ABS resin, polyacetal resin, etc. are preferable. The structure and size of the toner storage container are not particularly limited and can be appropriately selected depending on the purpose.
[0270] (Image forming apparatus and image forming method) The image forming apparatus of the present invention comprises at least an electrostatic latent image carrier, an electrostatic latent image forming means, and a developing means, and further comprises other means as necessary. The image forming method according to the present invention includes at least an electrostatic latent image forming step and a development step, and further includes other steps as necessary.
[0271] [Electrostatic latent image carrier] The material of the electrostatic latent image bearing member is not particularly limited and may be appropriately selected depending on the purpose, and examples thereof include inorganic photoreceptors such as amorphous silicon and selenium, and organic photoreceptors such as polysilane and phthalopolymethine, etc. Among these, amorphous silicon is preferred in terms of long life. The shape, structure and size of the electrostatic latent image bearing member are not particularly limited and may be appropriately selected from known shapes, structures and sizes. The linear speed of the electrostatic latent image bearing member is preferably 300 mm / s or more.
[0272] [Electrostatic latent image forming means and electrostatic latent image forming process] The electrostatic latent image forming means is not particularly limited as long as it is a means for forming an electrostatic latent image on the electrostatic latent image carrier, and may be appropriately selected depending on the purpose. For example, there may be mentioned a means having at least a charging member that charges the surface of the electrostatic latent image carrier, and an exposure member that exposes the surface of the electrostatic latent image carrier to light in an imagewise manner. The electrostatic latent image forming step is not particularly limited as long as it is a step of forming an electrostatic latent image on the electrostatic latent image bearing member, and can be appropriately selected depending on the purpose. For example, the electrostatic latent image forming step can be performed by charging the surface of the electrostatic latent image bearing member and then exposing it to light in an imagewise manner, using the electrostatic latent image forming means.
[0273] <Charging materials and charging> The charging member is not particularly limited and can be appropriately selected depending on the purpose. Examples of the charging member include a contact charger known per se having a conductive or semiconductive roller, brush, film, rubber blade, or the like, and a non-contact charger utilizing corona discharge such as a corotron or scorotron. The charging can be carried out, for example, by applying a voltage to the surface of the electrostatic latent image bearing member using the charging member. The shape of the charging member may be any shape, such as a roller, a magnetic brush, a fur brush, etc., and can be selected according to the specifications and shape of the image forming apparatus. The material, structure and size of the charging member are not particularly limited and can be appropriately selected from known materials.
[0274] The charging member is not limited to a contact-type charging member, but it is preferable to use a contact-type charging member in that an image forming apparatus in which the amount of ozone generated from the charging member is reduced can be obtained.
[0275] <Exposure member and exposure> The exposure member is not particularly limited as long as it can expose the surface of the electrostatic latent image carrier charged by the charging member in the shape of an image to be formed, and can be appropriately selected depending on the purpose. Examples of the exposure member include various exposure members such as a copying optical system, a rod lens array system, a laser optical system, and a liquid crystal shutter optical system. The light source used in the exposure member is not particularly limited and can be appropriately selected depending on the purpose. Examples of the light source include fluorescent lamps, tungsten lamps, halogen lamps, mercury lamps, sodium lamps, light-emitting diodes (LEDs), semiconductor lasers (LDs), electroluminescence (EL), and other light-emitting materials. In order to irradiate only light in a desired wavelength range, various filters such as a sharp cut filter, a band pass filter, a near infrared cut filter, a dichroic filter, an interference filter, and a color temperature conversion filter can be used. The material, shape, structure and size of the exposure member are not particularly limited and can be appropriately selected from known materials.
[0276] The exposure can be carried out, for example, by exposing the surface of the electrostatic latent image bearing member imagewise using the exposure member. In the present invention, a light back system may be adopted in which exposure is performed imagewise from the back side of the electrostatic latent image bearing member.
[0277] [Developing means and developing process] The developing unit is not particularly limited as long as it is a developing unit that develops the electrostatic latent image formed on the electrostatic latent image carrier to form a toner image, which is a visible image, and is equipped with a toner, and can be appropriately selected depending on the purpose. The developing step is not particularly limited as long as it is a step of developing the electrostatic latent image formed on the electrostatic latent image carrier with a toner to form a toner image, which is a visible image, and can be appropriately selected depending on the purpose. For example, the developing step can be performed by the developing means. The developing means is preferably a developing device having an agitator that frictionally agitates the toner to charge it, a magnetic field generating means fixed inside, and a developer carrier that can rotate and carries a developer containing the toner on its surface.
[0278] [Other means and other processes] Examples of the other means include a transfer means, a fixing means, a cleaning means, a discharging means, and a recycling means. Examples of the other steps include a transfer step, a fixing step, a cleaning step, a static elimination step, and a recycling step.
[0279] <Transfer means and transfer process> The transfer means is not particularly limited as long as it is a means for transferring a visible image onto a recording medium, and can be appropriately selected depending on the purpose. However, a preferred embodiment has a primary transfer means for transferring the visible image onto an intermediate transfer body to form a composite transfer image, and a secondary transfer means for transferring the composite transfer image onto a recording medium. The transfer step can be carried out by, for example, charging the visible image on the photoconductor using a transfer charger, and can be carried out by the transfer unit. The transfer step is not particularly limited as long as it is a step of transferring a visible image onto a recording medium, and may be appropriately selected depending on the purpose. However, a preferred embodiment is one in which an intermediate transfer body is used, a visible image is primarily transferred onto the intermediate transfer body, and then the visible image is secondarily transferred onto the recording medium.
[0280] Here, when the image to be secondarily transferred onto the recording medium is a color image made up of toners of multiple colors, the transfer means can be configured to sequentially overlay toners of each color on the intermediate transfer body to form an image on the intermediate transfer body, and the intermediate transfer means can be configured to secondarily transfer the image on the intermediate transfer body onto the recording medium all at once. The intermediate transfer body is not particularly limited and can be appropriately selected from known transfer bodies depending on the purpose. For example, a transfer belt is preferably used.
[0281] The transfer means (the primary transfer means, the secondary transfer means) preferably has at least a transfer device that peels and charges the visible image formed on the photoreceptor onto the recording medium. Examples of the transfer device include a corona transfer device using corona discharge, a transfer belt, a transfer roller, a pressure transfer roller, and an adhesive transfer device. The recording medium is typically plain paper, but is not particularly limited as long as it is capable of transferring an unfixed image after development, and can be appropriately selected according to the purpose. A PET base for overhead projectors can also be used.
[0282] <Fixing means and fixing process> The fixing means is not particularly limited as long as it is a means for fixing the transferred image transferred to the recording medium, and can be appropriately selected depending on the purpose, and is preferably, for example, a known heating and pressing member. Examples of the heating and pressing member include a combination of a heating roller and a pressing roller, and a combination of a heating roller, a pressing roller, and an endless belt. The fixing step can be carried out by the fixing means. The fixing step is not particularly limited as long as it is a step of fixing the visible image transferred to the recording medium, and can be appropriately selected depending on the purpose. For example, the fixing step may be performed for each color toner each time it is transferred to the recording medium, or may be performed simultaneously for each color toner in a stacked state.
[0283] The heating temperature in the heating and pressing member is preferably 80° C. or higher and 200° C. or lower. The image forming apparatus of the present invention may use, for example, a known optical fixing device together with or instead of the fixing means, depending on the purpose. The surface pressure in the fixing step is not particularly limited and can be appropriately selected depending on the purpose. 2 More than 80N / cm 2 It is preferable that:
[0284] <Cleaning means and cleaning process> The cleaning means is not particularly limited as long as it is capable of removing the toner remaining on the photoreceptor, and can be appropriately selected depending on the purpose. Examples of the cleaning means include a magnetic brush cleaner, an electrostatic brush cleaner, a magnetic roller cleaner, a blade cleaner, a brush cleaner, and a web cleaner. The cleaning step is not particularly limited as long as it is a step that can remove the toner remaining on the photoreceptor, and can be appropriately selected depending on the purpose. For example, the cleaning step can be performed by the cleaning unit.
[0285] <Static charge removal means and static charge removal process> The charge removing means is not particularly limited as long as it is a means for removing electricity by applying a charge removing bias to the photoconductor, and may be appropriately selected depending on the purpose. For example, a charge removing lamp may be used. The charge removing step is not particularly limited as long as it is a step of removing electricity by applying a charge removing bias to the photoconductor, and may be appropriately selected depending on the purpose. For example, the charge removing step may be performed by the charge removing unit.
[0286] <Recycling methods and processes> The recycling means is not particularly limited as long as it is a means for recycling the toner removed in the cleaning step to the developing device, and can be appropriately selected depending on the purpose. For example, a known transport means can be used. The recycling process is not particularly limited as long as it is a process for recycling the toner removed by the cleaning process back into the developing device, and can be appropriately selected depending on the purpose. For example, the recycling process can be performed by the recycling means.
[0287] Here, one embodiment of the method for forming an image by the image forming apparatus of the present invention will be described with reference to FIG. Although a printer is shown as an example of the image forming apparatus in this embodiment, the image forming apparatus is not particularly limited as long as it is capable of forming an image using toner, such as a copier, facsimile, multifunction machine, etc. The image forming apparatus includes a paper feed section 210, a conveying section 220, an image creating section 230, a transfer section 240, and a fixing unit 250. The paper feed section 210 includes a paper feed cassette 211 in which the paper P to be fed is stacked, and a paper feed roller 212 that feeds the paper P stacked in the paper feed cassette 211 one sheet at a time.
[0288] The conveying section 220 includes a roller 221 that conveys the paper P fed by the paper feed roller 212 toward the transfer section 240, a pair of timing rollers 222 that hold the leading end of the paper P conveyed by the roller 221 and wait to send the paper to the transfer section 240 at a predetermined timing, and a paper discharge roller 223 that discharges the paper P with the color toner image fixed thereto onto a paper discharge tray 224.
[0289] The image creating section 230 includes, spaced at a predetermined interval from left to right in the figure, an image forming unit 180Y that forms an image using a developer containing yellow toner, an image forming unit 180C that uses a developer containing cyan toner, an image forming unit 180M that uses a developer containing magenta toner, an image forming unit 180K that uses a developer containing black toner, and an exposure device 233. The image forming unit 180 (180Y, 180C, 180M, 180K) is arranged to be rotatable clockwise in the figure, and includes a photoconductor drum 231 (231Y, 231C, 231M, 231K) on which an electrostatic latent image and a toner image are formed, a charger 232 (232Y, 232C, 232M, 232K) that uniformly charges the surface of the photoconductor drum (231Y, 231C, 231M, 231K), and a cleaner 236 (236Y, 236C, 236M, 236K) that removes toner remaining on the surface of the photoconductor drum 231 (231Y, 231C, 231M, 231K). In addition, image forming units 180 (180Y, 180C, 180M, 180K) are provided with toner bottles 234 (234Y, 234C, 234M, 234K) that contain toner of each color, and sub-hoppers 160 (160Y, 160C, 160M, 160K) for replenishing the toner supplied from toner bottles 234 (234Y, 234C, 234M, 234K). Incidentally, when referring to any one of the image forming units 180 (180Y, 180C, 180M, 180K), it will be referred to as the image forming unit.
[0290] The exposure unit 233 irradiates the photosensitive drum 231 with laser light L emitted from a light source 233a based on image information by reflecting the light on a polygon mirror 233b (233bY, 233bC, 233bM, 233bK) that is rotated by a motor. The developer contains toner and carrier. The four image forming units 180 (180Y, 180C, 180M, 180K) have substantially the same mechanical configuration, except for the developer used therein.
[0291] The transfer unit 240 includes a drive roller 241 and a driven roller 242, an intermediate transfer belt 243 that can rotate counterclockwise in the figure as the drive roller 241 is driven, primary transfer rollers 244 (244Y, 244C, 244M, 244K) arranged opposite the photosensitive drums 231 (231Y, 231C, 231M, 231K) across the intermediate transfer belt 243, and secondary opposing rollers 245 and secondary transfer rollers 246 arranged opposite each other across the intermediate transfer belt 243 at the transfer position of the toner image to paper.
[0292] The fixing unit 250 has a heater installed inside and is equipped with a pressure roller 252 that forms a nip by rotatably pressing a fixing belt 251, which heats the paper P, against the fixing belt 251. This applies heat and pressure to the color toner image on the paper P, fixing the color toner image. The paper P with the fixed color toner image is discharged to a paper discharge tray 224 by a paper discharge roller 223, completing a series of image formation processes.
[0293] (Process cartridge) The process cartridge according to the present invention is molded so as to be detachably mountable to various image forming apparatuses, and has at least an electrostatic latent image carrier for carrying an electrostatic latent image, and a developing means for developing the electrostatic latent image carried on the electrostatic latent image carrier with the developer of the present invention to form a toner image. The process cartridge of the present invention may further have other means as necessary.
[0294] The developing means has at least a container for containing the developer of the present invention and a developer carrier for carrying and transporting the developer contained in the container. The developing means may further have a regulating member or the like for regulating the thickness of the developer carried.
[0295] One embodiment of the process cartridge is shown in Fig. 3. The process cartridge 110 includes a photosensitive drum 10, a corona charger 58, a developing device 40, a transfer roller 80, and a cleaning device 90, and further includes other means as necessary. In FIG. 3, the symbol L indicates a laser from an exposure device, and the symbol 95 indicates a recording paper. The photosensitive drum 10 may be the same as the electrostatic latent image carrier in the image forming apparatus. In the image forming process using the process cartridge shown in FIG. 3, while the photosensitive drum 10 rotates in the direction of the arrow, an electrostatic latent image corresponding to the exposed image is formed on its surface by charging the photosensitive drum 10 with a corona charger 58 and using a laser L from an exposure means (not shown). This electrostatic latent image is developed with toner by the developing device 40, and the toner developed image is transferred to recording paper 95 by the transfer roller 80 and printed out. Next, the surface of the latent image carrier after the image transfer is cleaned by the cleaning device 90, and further discharged by a discharging means (not shown), and the above operations are repeated again. EXAMPLES
[0296] Examples of the present invention will be described below, but the present invention is not limited to these examples. However, "parts" refers to "parts by mass" unless otherwise specified.
[0297] <Example 1> (Synthesis of amorphous polyester resin) The following materials were added to a 5 L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple under the following conditions: -material- Bisphenol A ethylene oxide side 2 mole adduct Bisphenol A propylene oxide 3 mole adduct Terephthalic acid Adipic Acid Trimethylolpropane -conditions- The molar ratio of bisphenol A ethylene oxide side 2 mole adduct to bisphenol A propylene oxide 3 mole adduct (bisphenol A ethylene oxide side 2 mole adduct / bisphenol A propylene oxide 3 mole adduct) is 85 / 15. The molar ratio of terephthalic acid to adipic acid (terephthalic acid / adipic acid) is 75 / 25. The amount of trimethylolpropane in all monomers is 1 mol%. The molar ratio (OH / COOH) of hydroxyl groups (OH) to carboxyl groups (COOH) is 1.2. Next, the mixture was reacted at 230°C for 4 hours under reduced pressure conditions of 10 mmHg or more and 15 mmHg or less, and then trimellitic anhydride was added to the reaction vessel so that the amount was 1 mol% relative to the total resin components. The mixture was reacted at 180°C for 3 hours under normal pressure conditions to obtain an "amorphous polyester resin."
[0298] (Preparation of Crystalline Polyester Resin Dispersion) <Synthesis of crystalline polyester resin> The following materials were added to a 5 L four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple under the following conditions: -material- Sebacic acid 1,6-Hexanediol -conditions- The molar ratio (OH / COOH) of hydroxyl groups (OH) to carboxyl groups (COOH) is 0.9. Titanium tetraisopropoxide was added so that the amount was 500 ppm relative to the total resin components, and the mixture was reacted at 180°C for 10 hours under normal pressure conditions, and then heated to 200°C and reacted for 3 hours. Next, the mixture was reacted at 200°C for 2 hours under a pressure of 8.3 kPa to obtain a "crystalline polyester resin."
[0299] <Preparation of Crystalline Polyester Resin Dispersion A> 60 parts by mass of "crystalline polyester resin" and 400 parts by mass of ethyl acetate were added to a container equipped with a stirring rod and a thermometer, and the mixture was heated to 80°C while stirring and maintained for 5 hours. After that, the mixture was cooled to 30°C over 1 hour, and dispersed using a bead mill (Ultraviscomill, manufactured by Imex) at a liquid delivery rate of 1 kg / hr, a disk peripheral speed of 6 m / sec, 80% by volume of zirconia beads with a diameter of 0.5 mm, and 3 passes to obtain "crystalline polyester resin dispersion A."
[0300] <Preparation of Crystalline Polyester Resin Dispersion B> 60 parts by mass of "crystalline polyester resin" and 400 parts by mass of ethyl acetate were added to a container equipped with a stirring rod and a thermometer, and the temperature was raised to 80°C while stirring and maintained for 5 hours. After that, the mixture was cooled to 30°C over 1 hour, and dispersed using a bead mill (Ultraviscomill, manufactured by Imex) under conditions of a liquid delivery rate of 1 kg / hr, a disk peripheral speed of 6 m / sec, 80% by volume of zirconia beads with a diameter of 0.5 mm, and 2 passes to obtain "crystalline polyester resin dispersion B".
[0301] (Synthesis of prepolymer) <Synthesis of intermediate polyester> Into a reaction vessel equipped with a condenser, stirrer and nitrogen inlet, the following materials were added under the following conditions: -material- 3-Methyl-1,5-pentanediol Isophthalic acid Adipic Acid Trimellitic anhydride -conditions- The molar ratio (OH / COOH) of hydroxyl groups (OH) to carboxyl groups (COOH) is 1.5. The diol component is composed of 100 mol% 3-methyl-1,5-pentanediol. The dicarboxylic acid component is composed of 40 mol% isophthalic acid and 60 mol% adipic acid. Trimellitic anhydride was added so that the amount of the total monomers was 1 mol%, and titanium tetraisopropoxide was added so that the amount was 1,000 ppm relative to the total resin components. Next, under normal pressure conditions, the temperature was raised to 200°C over about 4 hours, and then to 230°C over 2 hours, and the reaction was continued until no water was discharged. After that, the reaction was continued at 230°C for 5 hours under reduced pressure conditions of 10 mmHg to 15 mmHg, and an "intermediate polyester" was obtained.
[0302] <Synthesis of prepolymer> The "intermediate polyester" and isophorone diisocyanate (IPDI) were added to a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube so that the molar ratio (isocyanate groups of IPDI / hydroxyl groups of intermediate polyester) was 2.0, and the mixture was diluted with ethyl acetate to make a 50% ethyl acetate solution. The mixture was reacted at 100°C for 5 hours under normal pressure conditions to obtain a "prepolymer."
[0303] (Synthesis of amorphous hybrid resin) <Synthesis of amorphous polyester resin A> The following materials were added to a 5 L, four-neck flask equipped with a nitrogen inlet, a dehydrator, a stirrer, and a thermocouple: -material- 2,3-Butanediol 7.2g 1,2-Propanediol 6.08g Terephthalic acid 18.59g Tin(II) 2-ethylhexanoate 0.18g Nitrogen gas was introduced into the vessel to maintain an inert atmosphere and raise the temperature, and then the vessel was kept at 180°C for 1 hour under normal pressure conditions.The vessel was then heated from 180°C to 230°C at a rate of 10°C / hr, and further subjected to a condensation polymerization reaction at 230°C for 10 hours, followed by a reaction at 230°C for 1 hour at 8.0 kPa. Next, after cooling to 160° C., the following materials were added dropwise using a dropping funnel over a period of 1 hour. -material- Acrylic acid 0.9g Styrene 11.69g 2-Ethylhexyl acrylate 2.22g Dibutyl peroxide 3.00g After the dropwise addition, the temperature was kept at 160° C. and the addition polymerization reaction was allowed to proceed for 1 hour, after which the temperature was raised to 210° C. 6.92 g of trimellitic anhydride was added and reacted at 210° C. for 2 hours, and then the reaction was continued at 10 kPa and 210° C. until the desired softening point was reached, yielding "amorphous hybrid resin A." The SP value of the amorphous hybrid resin A was 10.6. The amorphous hybrid resin A had a weight average molecular weight of 110,000, a number average molecular weight of 3,100, a Tg of 50° C., and an acid value of 10.1 mgKOH / g.
[0304] <Synthesis of amorphous polyester resin B> The following materials were added to a 5 L, four-neck flask equipped with a nitrogen inlet, a dehydrator, a stirrer, and a thermocouple: -material- 2,3-Butanediol 7.2g 1,2-Propanediol 6.08g Terephthalic acid 18.59g Tin(II) 2-ethylhexanoate 0.18g Nitrogen gas was introduced into the vessel to maintain an inert atmosphere and raise the temperature, and then the vessel was kept at 180°C for 1 hour under normal pressure conditions.The vessel was then heated from 180°C to 230°C at a rate of 10°C / hr, and further subjected to a condensation polymerization reaction at 230°C for 10 hours, followed by a reaction at 230°C for 1 hour at 8.0 kPa. Next, after cooling to 160° C., a mixed liquid of the following materials was added dropwise using a dropping funnel over a period of 1 hour. -Materials (mixture)- Acrylic acid 0.6g Styrene 7.79g 2-Ethylhexyl acrylate 1.48g Dibutyl peroxide 3.00g After the dropwise addition, the temperature was kept at 160° C. and the addition polymerization reaction was allowed to proceed for 1 hour, after which the temperature was raised to 210° C. 4.61 g of trimellitic anhydride was added and reacted at 210° C. for 2 hours, and then the reaction was continued at 10 kPa and 210° C. until the desired softening point was reached, yielding "amorphous hybrid resin B." The SP value of the amorphous hybrid resin B was 10.8. The amorphous hybrid resin B had a weight average molecular weight (Mw) of 55,000, a number average molecular weight (Mn) of 2,800, a Tg of 55° C., and an acid value of 9.4 mgKOH / g.
[0305] (Synthesis of resin particles) <Production of Resin Fine Particle (A) Dispersion (W0-1)> The following materials were added to a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer, and the mixture was stirred at 200 rpm to homogenize. -material- ·Water 3710 parts by mass 200 parts by weight of polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium (Aqualon KH-1025, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) After heating to raise the temperature inside the system to 75° C., 90 parts by mass of a 10% by mass aqueous solution of ammonium persulfate was added, and then a mixed liquid of the following materials was added dropwise over 4 hours. -Materials (mixture)- Styrene 450 parts by weight Butyl acrylate 250 parts by weight Methacrylic acid 300 parts by weight After the dropwise addition, the mixture was aged at 75°C for 4 hours to obtain a "resin microparticle (A) dispersion (W0-1)" containing a resin (a1-1), which is a polymer copolymerized with the monomer and polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ester ammonium. The volume average particle size of the fine particles in the fine particle dispersion (W0-1) was 15 nm. A part of the fine particle dispersion (W0-1) was dried to isolate a resin (a1-1). The resin (a1-1) had a Tg of 53° C. and an acid value of 195 mg KOH / g. In addition, since the organic fine particles B in the present invention can be obtained by the same production method as that for the resin (a1-1), the resin (a1-1) was used as the organic fine particles (B-1).
[0306] <Production of Resin Fine Particle (A) Dispersion (W0-2)> The following materials were added to a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer, and the mixture was stirred at 200 rpm to homogenize. -material- ·Water 3760 parts by mass 150 parts by weight of polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ammonium (Aqualon KH-1025, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) After heating to raise the temperature inside the system to 75° C., 90 parts by mass of a 10% by mass aqueous solution of ammonium persulfate was added, and then a mixed liquid of the following materials was added dropwise over 4 hours. -Materials (mixture)- Styrene 430 parts by weight Butyl acrylate 270 parts by weight Methacrylic acid 300 parts by weight After the dropwise addition, the mixture was aged at 75°C for 4 hours to obtain a "resin microparticle (A) dispersion (W0-2)" containing a resin (a2-1), which is a polymer copolymerized with the monomer and polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ester ammonium. The volume average particle size of the fine particles in the fine particle dispersion (W0-2) was 30 nm. A part of the fine particle dispersion (W0-2) was dried to isolate a resin (a2-1). The resin (a2-1) had a Tg of 53° C. and an acid value of 195 mg KOH / g. In addition, since the organic fine particles B in the present invention can be obtained by the same production method as that for the resin (a2-1), the resin (a2-1) was used as the organic fine particles (B-2).
[0307] <Production of Resin Fine Particle (A) Dispersion (W0-3)> The following materials were added to a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer, and the mixture was stirred at 200 rpm to homogenize. -material- ·Water 3810 parts by mass 100 parts by weight of polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ester ammonium (Aqualon KH-1025, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) After heating to raise the temperature inside the system to 75° C., 90 parts by mass of a 10% by mass aqueous solution of ammonium persulfate was added, and then a mixed liquid of the following materials was added dropwise over 4 hours. -Materials (mixture)- Styrene 400 parts by weight Butyl acrylate 300 parts by weight Methacrylic acid 300 parts by weight After the dropwise addition, the mixture was aged at 75°C for 4 hours to obtain a "resin microparticle (A) dispersion (W0-3)" containing a resin (a3-1), which is a polymer copolymerized with the monomer and polyoxyethylene-1-(allyloxymethyl) alkyl ether sulfate ester ammonium. The volume average particle size of the fine particles in the fine particle dispersion (W0-3) was 45 nm. A part of the fine particle dispersion (W0-3) was dried to isolate a resin (a3-1). The resin (a3-1) had a Tg of 53° C. and an acid value of 195 mgKOH / g. In addition, since the organic fine particles B in the present invention can be obtained by the same production method as that for the resin (a3-1), the resin (a3-1) was used as the organic fine particles (B-3).
[0308] <Production of Resin Fine Particle (A-1) Dispersion (W-1)> The following materials were added to a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer. 0.267 parts by mass of tertiary butyl hydroperoxide (Perbutyl H, manufactured by NOF Corporation) was then added, and the mixture was heated until the temperature inside the system reached 70°C. -material- ·Resin fine particles (A) dispersion liquid (W0-1) 667 parts by mass ·Water 248 parts by mass Next, a mixture of the following materials was added dropwise over a period of 2 hours. -Materials (mixture)- Styrene 43.3 parts by weight Butyl acrylate 23.3 parts by weight 1% by weight ascorbic acid aqueous solution 18.0 parts by weight After the dropping, the mixture was matured at 70°C for 4 hours to obtain a "resin microparticle (A) dispersion (W0-1)" using the resin (a1-1) in the "resin microparticle (A) dispersion (W0-1)" as a seed, thereby obtaining a "resin microparticle (A-1) dispersion (W-1)" containing resin (a2-1), a polymer copolymerized from the monomer, and resin (a1-1) as constituent components within the same particle. The volume average particle diameter of the resin fine particles (A-1) was 17.3 nm. The fine particle dispersion (W-1) was neutralized with a 10% by mass aqueous ammonia solution to adjust the pH to 9.0, and then centrifuged to separate the precipitate, which was then dried to isolate a resin (a2-1). The Tg of the resin (a2-1) was 53°C.
[0309] <Production of Resin Fine Particle (A-2) Dispersion (W-2)> The following materials were added to a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer. 0.267 parts by mass of tertiary butyl hydroperoxide (Perbutyl H, manufactured by NOF Corporation) was then added, and the mixture was heated until the temperature inside the system reached 70°C. -material- ·Resin fine particles (A) dispersion liquid (W0-2) 667 parts by mass ·Water 248 parts by mass Next, a mixture of the following materials was added dropwise over a period of 2 hours. -Materials (mixture)- Styrene 43.3 parts by weight Butyl acrylate 23.3 parts by weight 1% by weight ascorbic acid aqueous solution 18.0 parts by weight After the dropping, the mixture was matured at 70°C for 4 hours. This resulted in the production of a "resin microparticle (A) dispersion (W0-2)" using the resin (a1-2) in the "resin microparticle (A) dispersion (W0-2)" as a seed, thereby obtaining a "resin microparticle (A-2) dispersion (W-2)" containing resin (a2-2), a polymer copolymerized from the monomer, and resin (a1-2) as constituent components within the same particle. The volume average particle diameter of the resin fine particles (A-2) was 34.3 nm. The fine particle dispersion (W-2) was neutralized with a 10% by mass aqueous ammonia solution to adjust the pH to 9.0, and then centrifuged to separate the precipitate, which was then dried to isolate a resin (a2-2). The Tg of the resin (a2-2) was 53°C.
[0310] <Production of Resin Fine Particle (A-3) Dispersion (W-3)> The following materials were added to a reaction vessel equipped with a stirrer, a heating / cooling device, and a thermometer. 0.267 parts by mass of tertiary butyl hydroperoxide (Perbutyl H, manufactured by NOF Corporation) was then added, and the mixture was heated until the temperature inside the system reached 70°C. -material- ·Resin fine particles (A) dispersion liquid (W0-3) 667 parts by mass ·Water 248 parts by mass Next, a mixture of the following materials was added dropwise over a period of 2 hours. -Materials (mixture)- Styrene 43.3 parts by weight Butyl acrylate 23.3 parts by weight 1% by weight ascorbic acid aqueous solution 18.0 parts by weight After the dropping, the mixture was matured at 70°C for 4 hours. This resulted in a "resin microparticle (A) dispersion (W0-3)" using the resin (a1-3) in the "resin microparticle (A) dispersion (W0-3)" as a seed to obtain a "resin microparticle (A-3) dispersion (W-3)" containing resin (a2-3), a polymer copolymerized from the monomers, and resin (a1-3) as constituent components within the same particle. The volume average particle diameter of the resin fine particles (A-3) was 51.5 nm. The fine particle dispersion (W-3) was neutralized with a 10% by mass aqueous ammonia solution to adjust the pH to 9.0, and then centrifuged to separate the precipitate, which was then dried to isolate a resin (a2-3). The Tg of the resin (a2-3) was 53°C.
[0311] (Preparation of Wax Dispersion) <Production of modified wax> The following materials were added to a pressure-resistant reaction vessel equipped with a stirrer, a heating / cooling device, a thermometer, and a dropping bomb, and after replacing the atmosphere with nitrogen, the temperature was raised to 170° C. with stirring. -material- Xylene 454 parts by weight 150 parts by weight of low molecular weight polyethylene (Sanyo Chemical Industries, Ltd., Sanwax LEL-400) Next, a mixture of the following materials was added dropwise over a period of 3 hours at 170°C, and the mixture was maintained at the same temperature for 30 minutes. -Materials (mixture)- Styrene 595 parts by weight Methyl methacrylate 255 parts by weight Di-t-butylperoxyhexahydroterephthalate 34 parts by mass Xylene 119 parts by weight Next, the xylene was distilled off under reduced pressure of 0.039 MPa to obtain a "modified wax." The SP value of the graft chain of the "modified wax" is 10.35 (cal / cm 3 ) 1 / 2 The number average molecular weight (Mn) was 1,900, the weight average molecular weight (Mw) was 5,200, and Tg was 57°C.
[0312] <Preparation of wax dispersion> 50 parts by mass of paraffin wax (HNP-9, hydrocarbon wax, melting point 75°C, SP value 8.8, manufactured by Nippon Seiro Co., Ltd.), 5 parts by mass of the "modified wax", and 165 parts by mass of ethyl acetate were added to a container equipped with a stirring rod and a thermometer, and the mixture was heated to 80°C while stirring and maintained for 5 hours. After that, the mixture was cooled to 30°C over 1 hour, and a "wax dispersion" was obtained by dispersing the mixture using a bead mill (Ultraviscomill, manufactured by Imex Co., Ltd.) under the conditions of a liquid delivery speed of 1 kg / hr, a disk peripheral speed of 6 m / sec, 80% by volume of zirconia beads with a diameter of 0.5 mm, and 3 passes.
[0313] (Preparation of Masterbatch) The following materials were added to a container and mixed using a Henschel mixer (manufactured by Mitsui Mining Co., Ltd.). -material- ·Water 1,200 parts by mass Carbon black (Printex 35 manufactured by Dexa) [DBP oil absorption = 42 mL / 100 mg, pH = 9.5] 500 parts by weight "Amorphous polyester resin" 500 parts by weight The resulting mixture was kneaded using two rolls at 150°C for 30 minutes, then rolled, cooled, and pulverized in a pulverizer to obtain a "master batch."
[0314] (Preparation of oil phase) 47 parts by weight of "crystalline polyester dispersion A", 49 parts by weight of "amorphous polyester resin", 6 parts by weight of "amorphous hybrid resin A", 17 parts by weight of "master batch", 21 parts by weight of "wax dispersion", and 30 parts of ethyl acetate were placed in a container and mixed at 5,000 rpm for 60 minutes using a TK Homomixer (manufactured by Tokushu Kika Co., Ltd.) to obtain an "oil phase".
[0315] (Preparation of aqueous phase) 256 parts by mass of water, 5 parts by mass of "Resin fine particle (A-1) dispersion (W-1)", 10 parts by mass of "Resin fine particle (A) dispersion (W0-1)", 26 parts by mass of 48.5% aqueous solution of sodium dodecyl diphenyl ether disulfonate (Eleminol MON-7: manufactured by Sanyo Chemical Industries, Ltd.), and 24 parts by mass of ethyl acetate were mixed and stirred to obtain a milky white liquid. This was designated as the "aqueous phase".
[0316] (Emulsification / solvent removal) To a vessel containing 32 parts by mass of the "oil phase", 5 parts by mass of the "prepolymer" and 0.2 parts by mass of isophoronediamine as a curing agent were added and stirred to obtain a mixed liquid. To the resulting mixture, 63 parts by mass of the "aqueous phase" was added, and the mixture was mixed for 20 minutes at 13,000 rpm using a TK homomixer to obtain an "emulsified slurry." Next, the "emulsified slurry" was placed in a container equipped with a stirrer and a thermometer, and the solvent was removed at 30°C for 8 hours, followed by aging at 45°C for 4 hours to obtain a "dispersed slurry."
[0317] (Washing and drying) 100 parts of the "dispersed slurry" was filtered under reduced pressure to obtain a "filter cake", and the following operations (1) to (4) were then carried out. (1) 100 parts by mass of ion-exchanged water was added to the "filter cake" and mixed with a TK homomixer (at 12,000 rpm for 10 minutes), and then filtered. (2) A 10% aqueous solution of sodium hydroxide was added to the “filter cake” from (1) until the pH reached 11, and the mixture was mixed in a TK homomixer (at 12,000 rpm for 30 minutes) and then filtered under reduced pressure. (3) 10% hydrochloric acid was added to the “filter cake” from (2) until the pH reached 4-5, and the mixture was mixed in a TK homomixer (at 12,000 rpm for 10 minutes) and then filtered. (4) 300 parts by mass of ion-exchanged water was added to the “filter cake” obtained after (3) and mixed in a TK homomixer (at a rotation speed of 12,000 rpm for 10 minutes), followed by filtration. The above steps (1) to (4) were repeated twice to obtain a "filter cake after washing treatment." The "filter cake after washing treatment" was dried in a circulating air dryer at 45° C. for 48 hours, and sieved through a mesh with 75 μm openings to obtain "toner base particles."
[0318] (External Addition Treatment) 100 parts by weight of the "toner base particles" were mixed in a Henschel mixer with 0.6 parts by weight of hydrophobic silica having an average particle size of 100 nm, 1.0 parts by weight of titanium oxide having an average particle size of 20 nm, and 0.8 parts by weight of hydrophobic silica fine powder having an average particle size of 15 nm to obtain "Toner 1."
[0319] (Preparation of developer) <Preparation of carrier> 100 parts by mass of silicone resin (organo straight silicone), 5 parts by mass of γ-(2-aminoethyl)aminopropyltrimethoxysilane, and 10 parts by mass of carbon black were added to 100 parts by mass of toluene, and dispersed for 20 minutes with a homomixer to prepare a resin layer coating liquid. Using a fluidized bed type coating device, the resin layer coating liquid was applied to the surface of 1,000 parts by mass of spherical magnetite with an average particle size of 50 μm to prepare a "carrier".
[0320] <Preparation of developer> Using a ball mill, 5 parts by mass of the "toner 1" and 95 parts by mass of the "carrier" were mixed to prepare "developer 1".
[0321] <Example 2> In the preparation of the oil phase, the amount of "resin fine particle (A-1) dispersion liquid (W-1)" was changed from 5 parts by mass to 4.7 parts by mass, and the amount of "resin fine particle (A) dispersion liquid (WO-1)" was changed from 10 parts by mass to 10.3 parts by mass, but the procedure was the same as in Example 1 to prepare "toner 2." Five parts by mass of the "toner 2" and 95 parts by mass of the "carrier" were mixed to prepare "developer 2."
[0322] <Example 3> During the preparation of the oil phase, "resin fine particle (A-1) dispersion (W-1)" was changed to "resin fine particle (A-2) dispersion (W-2)" and "resin fine particle (A) dispersion (WO-1)" was changed to "resin fine particle (A) dispersion (WO-2)," but "toner 3" was prepared in the same manner as in Example 1. Five parts by mass of the "toner 3" and 95 parts by mass of the "carrier" were mixed to prepare "developer 3."
[0323] <Example 4> In the preparation of the oil phase, "amorphous hybrid resin A" was changed to "amorphous hybrid resin B", and "resin fine particle (A-1) dispersion liquid (W-1)" was changed from 5 parts by mass to 4.8 parts by mass, and "resin fine particle (A) dispersion liquid (WO-1)" was changed from 10 parts by mass to 10.2 parts by mass, but the procedure was the same as in Example 1 to prepare "toner 4". Five parts by mass of the "toner 4" and 95 parts by mass of the "carrier" were mixed to prepare "developer 4".
[0324] <Example 5> In the preparation of the oil phase, "amorphous hybrid resin A" was changed to "amorphous hybrid resin B", "resin fine particle (A-1) dispersion liquid (W-1)" to "resin fine particle (A-3) dispersion liquid (W-3)", and "resin fine particle (A) dispersion liquid (WO-1)" to "resin fine particle (A) dispersion liquid (WO-3)", but the procedure was the same as in Example 1 to prepare "toner 5". Five parts by mass of the "toner 5" and 95 parts by mass of the "carrier" were mixed to prepare "developer 5".
[0325] <Example 6> "Toner 6" was prepared in the same manner as in Example 1, except that in (Preparation of Oil Phase), 6 parts by mass of "Amorphous Hybrid Resin A" was changed to 5 parts by mass. 5 parts by mass of the "Toner 6" was mixed with 95 parts by mass of the "Carrier" to prepare "Developer 6".
[0326] <Example 7> "Toner 7" was prepared in the same manner as in Example 1, except that in (Preparation of oil phase), 6 parts by mass of "Amorphous hybrid resin A" was replaced with 5 parts by mass of "Amorphous hybrid resin B". 5 parts by mass of the "Toner 7" was mixed with 95 parts by mass of the "Carrier" to prepare "Developer 7".
[0327] <Example 8> In the preparation of the oil phase, the amount of "resin fine particle (A-1) dispersion liquid (W-1)" was changed from 5 parts by mass to 3.0 parts by mass, and the amount of "resin fine particle (A) dispersion liquid (WO-1)" was changed from 10 parts by mass to 12 parts by mass, but the procedure was the same as in Example 1 to prepare "toner 8". Five parts by mass of the "toner 8" and 95 parts by mass of the "carrier" were mixed to prepare "developer 8".
[0328] <Example 9> In the preparation of the oil phase, "Toner 9" was prepared in the same manner as in Example 1, except that 6 parts by mass of "Amorphous Hybrid Resin A" was replaced with 5 parts by mass of "Amorphous Hybrid Resin B", and 5 parts by mass of "Resin Fine Particle (A-1) Dispersion (W-1)" was replaced with 3.0 parts by mass, and 10 parts by mass of "Resin Fine Particle (A) Dispersion (WO-1)" was replaced with 12 parts by mass. 5 parts by mass of the "Toner 9" was mixed with 95 parts by mass of the "Carrier" to prepare "Developer 9".
[0329] <Comparative Example 1> In the preparation of the oil phase, "Toner 10" was prepared in the same manner as in Example 1, except that the amount of "Amorphous Hybrid Resin A" was changed from 6 parts by mass to 4 parts by mass. "Developer 10" was prepared by mixing 5 parts by mass of the "Toner 10" and 95 parts by mass of the "Carrier".
[0330] <Comparative Example 2> In the preparation of the oil phase, "Toner 11" was prepared in the same manner as in Example 1, except that 6 parts by mass of "Amorphous Hybrid Resin A" was replaced with 4 parts by mass of "Amorphous Hybrid Resin B". 5 parts by mass of the "Toner 11" was mixed with 95 parts by mass of the "Carrier" to prepare "Developer 11".
[0331] <Comparative Example 3> In the preparation of the oil phase, 6 parts by mass of "amorphous hybrid resin A" was replaced with 5 parts by mass of "amorphous hybrid resin B", and 5 parts by mass of "resin fine particle (A-1) dispersion liquid (W-1)" was replaced with 2.8 parts by mass, and 10 parts by mass of "resin fine particle (A) dispersion liquid (WO-1)" was replaced with 12.2 parts by mass, but the procedure was the same as in Example 1 to prepare "toner 12". 5 parts by mass of the "toner 12" was mixed with 95 parts by mass of the "carrier" to prepare "developer 12".
[0332] <Comparative Example 4> In (Preparation of oil phase), the amount of "amorphous hybrid resin A" was changed from 6 parts by mass to 2 parts by mass, and the amount of "resin fine particle (A-1) dispersion liquid (W-1)" was changed from 5 parts by mass to 2.8 parts by mass, and the amount of "resin fine particle (A) dispersion liquid (WO-1)" was changed from 10 parts by mass to 12.2 parts by mass, but the procedure was the same as in Example 1 to prepare "toner 13". 5 parts by mass of the "toner 13" and 95 parts by mass of the "carrier" were mixed to prepare "developer 13".
[0333] <Comparative Example 5> "Toner 14" was prepared in the same manner as in Example 1, except that in (Preparation of oil phase), 49 parts by mass of "amorphous polyester resin" was changed to 96 parts by mass, and "Crystalline polyester resin dispersion A" was not included. 5 parts by mass of the "Toner 14" and 95 parts by mass of the "Carrier" were mixed to prepare "Developer 14".
[0334] <Comparative Example 6> "Toner 15" was prepared in the same manner as in Example 1, except that the "wax dispersion" was not used during (preparation of oil phase). 5 parts by mass of the "Toner 15" and 95 parts by mass of the "Carrier" were mixed to prepare "Developer 15".
[0335] <Comparative Example 7> "Toner 16" was prepared in the same manner as in Example 1, except that in (Preparation of oil phase), "Crystalline polyester resin dispersion A" was changed to "Crystalline polyester resin dispersion B". 5 parts by mass of the "Toner 16" and 95 parts by mass of the "Carrier" were mixed to prepare "Developer 16".
[0336] (Measurement of maximum domain diameter of crystalline polyester resin) The obtained toners 1 to 16 were thoroughly dispersed in a room temperature curing epoxy resin (Devcon DEV-TUBE), and then left for one day or more to cure the epoxy resin, obtaining a cured product with the toner embedded therein. The cross section of the cured product was exposed using a microtome (Leica EM UC7) equipped with a diamond blade, and the cured product with the exposed cross section was immersed for three hours in an organic solvent (hexane) in which only the release agent dissolves, dissolving only the domains of the release agent. After that, the cured product was dried for one day or more, and then thin-film slices were cut out under the following cutting conditions, and the obtained thin-film slices were stained with ruthenium tetroxide. -Cutting conditions- Cutting thickness: 100nm ·Cutting speed 0.05~0.2 mm / sec Uses a diamond knife (Ultra Sonic 35°) The slice was adjusted so that one slice contained cross sections of about 50 toner particles or toner particles. A transmission electron microscope (TEM) was used to observe and photograph the cross-sectional image of the toner at a magnification of 30,000 times, and a TEM image of the cross-section of the toner was prepared. The obtained TEM image was binarized (threshold 80 / 255 steps) using image analysis software "Image-J", and the major axis of all crystalline polyester resin domains present in the cross-section of the toner was measured. In addition, 100 toner particles whose major axis in the TEM image corresponds to the average particle diameter of the produced toner were selected, and the major axis of the crystalline polyester resin domain was measured. From the measurement results, the ratio of the crystalline polyester resin domains whose maximum diameter exceeds 1.0 μm was obtained. The results are shown in Tables 1 to 4. The observation conditions for the transmission electron microscope were as follows: -Observation conditions- Equipment: JEOL Transmission Electron Microscope JEM-2100F Acceleration voltage: 200kV Morphological observation: bright field method ·Setting conditions spot size:3,CLAP:1,OLAP:3,Alpha:3
[0337] (Standard deviation of distance between resin particles) 50 ml of a 5% aqueous solution containing a surfactant (product name: Noigen ET-165, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) was added to a 100 ml screw tube, and 3 g of the obtained toners 1 to 16 were added to the mixture and gently moved up and down and left and right. After that, the mixture was stirred for 30 minutes in a ball mill so that the toners would blend into the dispersion solution. Next, in order to liberate the external additives, ultrasonic energy was applied under the following conditions using an ultrasonic homogenizer (product name: homogenizer, model VCX750, CV33, manufactured by SONICS & MATERIALS Co., Ltd.). -Ultrasonic conditions- Vibration time: 60 minutes continuous Output: 40W ·Amplitude 40W ·Vibration start temperature 23℃±1.5℃ ·Temperature during vibration 23℃±1.5℃ The dispersion to which ultrasonic energy had been applied was suction filtered using filter paper (product name: Qualitative Filter Paper (No. 2, 110 mm), manufactured by Advantec Toyo Co., Ltd.), washed twice with ion-exchanged water, and then filtered again to remove the liberated additives, after which the toner particles were dried. The toner particles obtained after drying were observed with a scanning electron microscope (SEM). First, the external additives and charge control agent containing Si were detected by observing the reflected electron image, and the reflected electron image was photographed. The reflected electron image obtained was binarized (threshold: 135) using the image processing software "Image-J" to create an image in which the external additives and the charge control agent were excluded. Next, a secondary electron image was observed at the same position as the backscattered electron image, and the secondary electron image was taken. The backscattered electron image, from which the external additives and the charge control agent were removed, was compared with the secondary electron image to determine that the particles present in the areas other than the remaining external additives and the remaining charge control agent were resin particles. The distance between the resin particles was measured using the image processing software "Image-J." The scanning electron microscope images were taken under the following conditions. --Filming conditions-- Scanning electron microscope SU-8230 Magnification: 35,000x Image capture: SE (L) secondary electrons, BSE (backscattered electrons) Acceleration voltage: 2.0 kV ·Acceleration current 1.0μA ·Probe current Normal Focus Mode UHR Working distance 8.0mm The standard deviation in the distance between the resin particles was calculated by the following formula, where the distance between the particles is x. The results are shown in Tables 1 to 4.
[0338]
number
[0339] (Toner Evaluation) <Low temperature fixability> The obtained developers 1 to 16 were loaded into the image forming apparatus shown in FIG. 2, and a rectangular solid image of 2 cm×15 cm was printed on PPC paper type 6000<70W>A4 T (manufactured by Ricoh Co., Ltd.) in a monochrome mode with a toner adhesion amount of 0.8 mg / cm 2 When forming a solid image, an image forming apparatus without a thermal fixing unit was used. The solid image was formed on the transfer paper at a position 3.0 cm from the leading edge in the paper feed direction. The toner adhesion amount is 0.8 mg / cm 2 If so, other methods may be used. Under the following conditions, observation was made as to whether offset occurred, in which a residual image of a solid image was fixed in a place other than the desired place, and the temperature at which cold offset occurred (MFT) was measured and then evaluated based on the following evaluation criteria. The results are shown in Tables 1 to 4. Note that the lower the temperature at which cold offset occurred, the better the low-temperature fixability. -conditions- Fixing speed (heat roller peripheral speed) 213mm / sec Fixing pressure (pressure roller pressure) 10kg / cm 2 -Cold offset evaluation criteria- ◎: Minimum fixing temperature is 130℃ or less ○: The minimum fixing temperature is greater than 130°C and less than or equal to 135°C. △: The minimum fixing temperature is greater than 135°C and less than 140°C ×: The minimum fixing temperature is higher than 140° C.
[0340] <Heat-resistant storage stability> 10 g of the obtained toners 1 to 16 were filled into a 50 mL glass container, and the toner was stored at 50° C. for 8 hours, after which it was sieved through a 42 mesh sieve for 2 minutes, and the mass of the toner remaining on the wire mesh (sieve) was measured, and the toner residual rate was measured from the ratio to the mass of the toner placed in the sieve [(mass of toner remaining on the wire mesh / mass of toner placed in the sieve)×100]. The results are shown in Tables 1 to 4. At this time, the better the heat resistance storage stability of the toner, the smaller the residual rate. The evaluation criteria for heat-resistant storage stability were as follows: --Evaluation criteria for survival rate-- ◎: Residual rate is less than 5% ○: Residual rate is 5% or more and less than 15% △: Residual rate is between 15% and 30% ×: Residual rate is 30% or more
[0341] <Cleaning ability (photoreceptor contamination)> The obtained developers 1 to 16 were loaded into the image forming apparatus shown in FIG. 2, and output was performed under the following conditions. -conditions- ·Environment 21℃ / 65%RH -Paper feed conditions: 5% image coverage chart printed 3 times / job Output capacity: 50,000 sheets (A4 landscape size) Thereafter, in a laboratory environment of 32°C and 54% RH, a vertical stripe pattern (relative to the paper travel direction) of 43 mm width and three charts were printed on 100 sheets of A4 size landscape. The images and photoreceptors obtained by printing again were observed visually and with a laser microscope (LEXT OLS4500, manufactured by Olympus Corporation), and the cleaning properties were evaluated based on the following evaluation criteria. The results are shown in Tables 1 to 4. --Cleaning performance evaluation criteria-- ⊚: Toner that has slipped through due to poor cleaning cannot be visually confirmed on either the printed paper or the photoconductor, and no streaks of toner can be confirmed even when the photoconductor is observed longitudinally under a microscope. ◯: Toner that has slipped through due to poor cleaning cannot be visually confirmed on either the printed paper or the photoconductor, but streaks of toner can be confirmed when the photoconductor is observed longitudinally under a microscope. ×: Toner that has slipped through due to poor cleaning can be visually confirmed on the printed paper and on the photoconductor.
[0342] <Filming of external additives (inorganic fine particles)> The obtained developers 1 to 16 were loaded into the image forming apparatus shown in FIG. 2, and output was performed under the following conditions. -conditions- ·Environment 27℃ / 90%RH -Paper feed conditions: 30% image coverage chart printed 3 times / job Output capacity: 5,000 sheets (A4 landscape size) After that, 5,000 sheets (A4 size landscape) of blank paper were output at 3 prints / job, and then one halftone image was printed, and the image and photoreceptor were visually observed. The results are shown in Tables 1 to 4. --Filming evaluation criteria-- .circle.: No filming occurred, no problems with the photoconductor, and no problems with image quality. ◯: Thin filming is observed in the printing direction, but is at a level that does not pose a problem in terms of image quality. ×: Filming is clearly observed on the photoreceptor, and is at a level that is problematic in terms of image quality.
[0343] [Table 1]
[0344] [Table 2]
[0345] [Table 3]
[0346] [Table 4]
[0347] For example, aspects of the present invention are as follows. <1> A toner having resin particles on the surface of a toner base particle containing at least a crystalline polyester resin, an amorphous polyester resin, a colorant, and a release agent, the maximum diameter of a domain of a crystalline polyester resin of the toner observed by a transmission electron microscope (TEM) is 1.5 μm or less; Among the domains of the crystalline polyester resin present in the toner, a ratio of the domains of the crystalline polyester resin having a maximum diameter of more than 1.0 μm is 10% or less, The toner is characterized in that, among the adjacent resin particles present on the surface of the toner base particle, the standard deviation of the distance between the resin particles that are not in contact with each other is less than 600 nm. <2> The toner contains an amorphous hybrid resin. <1> The toner is as described above. <3> The resin particles contain a vinyl-based unit. <1> From the above <2> The toner according to any one of claims 1 to 5, <4> The resin particles contain at least a styrene-acrylic resin having a carboxylic acid. <1> From the above <3> The toner according to any one of claims 1 to 5, <5> The maximum diameter of the domain of the crystalline polyester resin is 1.2 μm or less. <1> From the above <4> 2. The toner according to claim 1, <6> Among the domains of the crystalline polyester resin present in the toner, the ratio of the domains of the crystalline polyester resin having a maximum diameter exceeding 1.0 μm is 5% or less; <1> From the above <5> The toner according to any one of claims 1 to 5, <7> the toner has a glass transition temperature (Tg1st) in a first temperature rise measured by differential scanning calorimetry (DSC) of 40° C. or higher and 65° C. or lower; the glass transition temperature (Tg1st) of the first temperature rise of the DSC of the component of the toner that is insoluble in tetrahydrofuran (THF) is -45°C or more and 5°C or less; The THF-soluble component of the toner has a glass transition temperature (Tg2nd) at the second temperature rise in DSC of 20° C. or more and 65° C. or less. <1> From the above <6> The toner according to any one of claims 1 to 5, <8> The amorphous polyester resin contains a modified polyester resin. <1> From the above <7> The toner according to any one of claims 1 to 5, <9> The above <1> From the above <8> 2. A toner storage container comprising the toner according to claim 1, wherein the toner is a toner containing material. <10> a latent electrostatic image carrier; an electrostatic latent image forming unit that forms an electrostatic latent image on the latent electrostatic image carrier; and a developing unit that is provided with a toner and that develops the electrostatic latent image formed on the latent electrostatic image carrier to form a visible image, The toner is <1> From the above <8> 2. An image forming apparatus comprising the toner according to claim 1.
[0348] The above <1> From the above <8> The toner according to any one of the preceding claims. <9> The toner storage container according to <10> According to the image forming apparatus described in the above, the conventional problems can be solved and the object of the present invention can be achieved. [Explanation of symbols]
[0349] 10 Photoconductor drum 40 Developer 58 Corona charger 80 Transfer roller 90 Cleaning Equipment 95 Recording Paper 110 Process cartridge 160Y Sub hopper (yellow) 160C Sub hopper (cyan) 160M Sub Hopper (Magenta) 160K Subhopper (Black) 180Y Image forming unit (yellow) 180C Image forming unit (cyan) 180M Image forming unit (magenta) 180K Image Forming Unit (Black) 210 Paper feed section 211 Paper feed cassette 212 Paper feed roller 220 Conveyor 221 Lola 222 Timing roller 223 Paper ejection roller 224 Paper output tray 230 Image creation section 231Y Photoconductor drum (yellow) 231C Photoconductor drum (cyan) 231M Photoconductor Drum (Magenta) 231K Photoconductor drum (black) 232Y Charger (Yellow) 232C Charger (cyan) 232M Charger (Magenta) 232K Charger (Black) 233 Exposure device 233a light source 233bY Polygon mirror (yellow) 233bC Polygon mirror (cyan) 233bM Polygon Mirror (Magenta) 233bK Polygon Mirror (Black) 234Y Toner bottle (yellow) 234C Toner bottle (cyan) 234M Toner Bottle (Magenta) 234K Toner Bottle (Black) 236Y Cleaning machine (yellow) 236C Cleaning Machine (Cyan) 236M Cleaner (Magenta) 236K Cleaning Tool (Black) 240 Transcription Unit 241 Drive roller 242 Driven roller 243 Intermediate transfer belt 244 Primary transfer roller 244Y Primary transfer roller (yellow) 244C Primary transfer roller (cyan) 244M Primary transfer roller (magenta) 244K Primary transfer roller (black) 245 Secondary opposing roller 246 Secondary transfer roller 250 Fixing unit 251 Fixing belt 252 Pressure roller L Laser P paper [Prior art documents] [Patent documents]
[0350] [Patent Document 1] JP 2004-46095 A [Patent Document 2] JP 2007-271789 A [Patent Document 3] Patent No. 5884797 [Patent Document 4] JP 2015-118151 A [Patent Document 5] JP 2016-164616 A [Patent Document 6] Patent No. 6233332 [Patent Document 7] Patent No. 5879772 [Patent Document 8] JP 2019-099809 A [Patent Document 9] JP 2019-143128 A [Patent Document 10] JP 2015-148724 A
Claims
1. A toner having resin particles on the surface of toner base particles containing at least a crystalline polyester resin, an amorphous polyester resin, an amorphous hybrid resin in which a polyester resin and a styrene-acrylic resin are partially chemically bonded, a colorant, and a release agent, the maximum diameter of a domain of a crystalline polyester resin of the toner observed by a transmission electron microscope (TEM) is 1.5 μm or less; Among the domains of the crystalline polyester resin present in the toner, a ratio of the domains of the crystalline polyester resin having a maximum diameter of more than 1.0 μm is 10% or less, The toner, wherein the standard deviation of the distance between adjacent resin particles that are not in contact with each other and that are present on the surface of the toner base particle is less than 600 nm.
2. The toner according to claim 1 , wherein the resin particles contain a vinyl-based unit.
3. 3. The toner according to claim 1, wherein the resin particles contain at least a styrene-acrylic resin having a carboxylic acid.
4. 4. The toner according to claim 1, wherein the maximum diameter of the domain of the crystalline polyester resin is 1.2 [mu]m or less.
5. 5. The toner according to claim 1, wherein a ratio of domains of the crystalline polyester resin having a maximum diameter exceeding 1.0 μm to domains of the crystalline polyester resin present in the toner is 5% or less.
6. the toner has a glass transition temperature (Tg1st) in a first temperature rise measured by differential scanning calorimetry (DSC) of 40° C. or higher and 65° C. or lower; the glass transition temperature (Tg1st) of the component of the toner that is insoluble in tetrahydrofuran (THF) during the first temperature rise in DSC is −45° C. or higher and 5° C. or lower; 6. The toner according to claim 1, wherein a THF-soluble component of the toner has a glass transition temperature (Tg2nd) in a second heating run of DSC of 20° C. or more and 65° C. or less.
7. The toner according to claim 1 , wherein the amorphous polyester resin contains a modified polyester resin.
8. A toner storage container, which stores the toner according to any one of claims 1 to 7.
9. a latent electrostatic image carrier; an electrostatic latent image forming unit that forms an electrostatic latent image on the latent electrostatic image carrier; and a developing unit that is provided with a toner and that develops the latent electrostatic image formed on the latent electrostatic image carrier to form a visible image, 8. An image forming apparatus, comprising the toner according to claim 1.
Citation Information
Patent Citations
Schottky gate field-effect transistor
JP1983079772A
Method of treating tip of binding thread of japanese bound booklet
JP1983084797A
JP1987033332A
Color toner for developing electrostatic charge image
JP2004046095A
Toner binder and toner
JP2007271789A